Who Cares? The Impact of Neoliberal Policies and New Organizational Methods on Child and Youth Workers - Altass, Patricia D. (University of Guelph, 2009)
Child and Youth Work is an emotionally demanding profession with an extremely high burnout rate. Previous research has shown that there are a variety of factors that contribute to high rates of burnout within this profession. This thesis begins by exploring topics related to stress, burnout, emotional labour and vicarious trauma, providing a context to understand the inherent issues and challenges faced by workers in this field. The prevailing beliefs and values underlying neoliberal policies resulting in funding restrictions within the social services are then considered in relation to the impact of these policies on experienced levels of worker stress and burnout with the residential care field. Lastly, this thesis looks at the introduction of new organizational methods, specifically Total Quality Management and New Public Management, as strategies implemented by agencies to cope with funding limitations, and the resulting impact on levels of stress and burnout of front line residential child care workers. In addition to the three key areas of focus, the role and impact of unions within residential treatment settings is considered as a potential avenue for positive change within these workplaces.

Farm-Level Impacts in Mexico of the Participation in Canada's Seasonal Agricultural Workers Program (CSWAP) - Carvajal, Lidia (University of Guelph, 2009)
In several parts of the world, the number of poor people in rural areas surpasses the capacity of agriculture to provide employment opportunities. The increasing role of off-farm income has highlighted the importance of rural migration, both within Mexico and to the United States (US) and Canada, as a vehicle for poverty reduction. A significant number of Mexican migrants are participating in guest worker programs, performing mainly agricultural activities. These programs allow Mexicans to enter the US and Canada through formal channels. Canada's Seasonal Agricultural Workers' Program (CSAWP) lets Mexican farmers enter Canada to work legally in agriculture, and participants in this Program send remittances home that are an important contribution to rural development. The main reasons to participate in guest worker programs relate to economic factors, such as the opportunity to earn a relatively high, stable income abroad and the lack of employment opportunities in Mexico, particularly in rural areas. The number of Mexican agricultural workers temporally migrating to Canada through CSAWP has increased significantly over time and now exceeds 12,000 annually. In Mexico, the program provides an estimated C$70 million in remittance income annually, mainly directed to rural and poorer regions. In these regions, this fungible income supports consumption activities and expenditures on family education. However, there are also investments in farming activities, in turn enhancing agrarian incomes. This research explores the impact of remittances on farm investments by migrant workers participating in CSAWP, which in turn impact farm income levels. The results highlight the extent to which temporary migrant labour to Canadian agriculture allows Mexican farmers to enhance their agricultural activities through increased farm investments, such as buying better seeds, fertilizer and farm equipment. The results show that, on the one hand, remittances can significantly enhance farm investments in Mexico that in turn increase farm incomes and, on the other, remittances increase non-farm incomes in Mexico, allowing farm migrants to expand their income portfolio. Hence, these results support the New Economics of Labour Migration (NELM) hypothesis that remittances relax the liquidity constraint in production/investment decisions. Furthermore, family labour availability counterbalances any temporary labour loss because of migration.
Keywords: Canada; Farm-level; Mexico; Seasonal Agricultural Workers Program; Social sciences

Benchmarking Carrots and Sticks: Developing a Model for the Evaluation of Work-Based Employment Programs - Castonguay, Julie (Hugo Sinzheimer Institute, University of Amsterdam, 2009)
Social benchmarking is an evaluation method in which the performance levels of different public social programs are compared, either relatively to each other or to an absolute value. The first part of this research discusses the use of social benchmarking for the evaluation of active labour market policies. This part also develops a social benchmark model, which can be used to assess the performance of active labour market policies in general, and work-based employment programs in specific. The second part of this research consists of the actual benchmarking of the work-based employment programs in five countries: Australia, Canada, the Netherlands, Switzerland and the United Kingdom.

Les jeunes migrants québécois dans les vallées fruitières de la Colombie-Britannique : ethnographie d'une forme de mobilité - Couture, Hugo (Laval, 2009)
Le groupe des jeunes voyageurs combinant le travail dans leur expérience de voyage constitue le segment du marché touristique mondial qui enregistre la croissance la plus importante cette dernière décennie. Certaines économies régionales dépendent de cette force de travail temporaire. C'est le cas de l'industrie agricole des vallées de l'Okanagan-Similkameen et de Creston en Colombie-Britannique qui accueille annuellement des milliers de migrant fruit pickers provenant majoritairement du Québec. Ce mémoire porte sur le quotidien de ces jeunes québécois et s'attarde à comprendre le sens qu'ils accordent à leurs projets de mobilité. Sur la base d'entretiens, je dégage l'imaginaire commun, les mythes, les idéaux et les représentations qui ont incité les jeunes à partir: Les résultats indiquent que ces jeunes inscrivent leur mouvement dans une double logique de quête et de fuite et que le sens attribué à l'expérience de vacances-travail diffère entre les nouveaux arrivants et ceux qui reviennent d'année en année.

Pour un syndicalisme de lutte de classe! : les groupes marxistes-léninistes et le mouvement syndical au Québec, 1972-1983 - Dubois-Campagna, Alexis (Université de Sherbrooke, 2009)
Dès la fin des années 1960, se développe une nouvelle tendance socialiste au Québec dans un contexte marqué par l'épuisement de la Révolution tranquille et par une ébullition idéologique sur la scène internationale. Dans ce climat politique, des groupuscules marxistes-léninistes (m-l) de tendance maoïste voient le jour au Québec, principalement dans la deuxième moitié des années 1970. Au même moment, sur le front syndical québécois, la lutte est intense entre travailleurs et employeurs. Les fronts communs de 1972 et 1975 et d'importantes grèves en font foi. De plus, de nombreux chefs syndicaux n'hésitent pas à s'attaquer directement au patronat et à l'État dans des discours clairement nourris par l'idéologie socialiste. Le radicalisme politique, même s'il n'est pas homogène et généralisé dans les centrales québécoises, s'impose de plus en plus dans les syndicats locaux comme dans les instances supérieures. C'est précisément les liens entre ces deux mondes, celui des groupuscules marxistes-léninistes et celui des centrales syndicales, qui nous intéressent. L'originalité de notre travail tient au fait qu'il lie les historiographies du marxisme-léninisme et du syndicalisme, ce qui représente un angle intéressant afin de renouveler la réflexion dans ces deux champs de recherche, certes très proches, mais malheureusement trop souvent étanches. À l'aide de diverses sources écrites, notamment les publications des organisations m-l et les archives des mêmes groupes, mais aussi d'entrevues menées par l'auteur avec d'anciens militants syndicaux, nous observons les relations entre les deux principaux groupuscules marxistes-léninistes, à savoir En Lutte! et la Ligue communiste (marxiste-léniniste) du Canada, et les centrales syndicales québécoises entre 1972 et 1983. Effectivement, il nous semble pertinent de mieux comprendre la nature des liens et des influences réciproques entre ces acteurs sociaux. L'objectif premier de cette recherche est de mettre en relief le militantisme des marxistes-léninistes au sein de ces institutions syndicales. En effet, la structure ouverte des syndicats, c'est-à-dire démocratique et accessible à tous les travailleurs syndiqués, a permis à un grand nombre de membres et sympathisants m-l de s'y intégrer et d'y faire valoir des positions d'extrême gauche. Et c'est justement le militantisme soutenu des m-l qui, contrastant avec celui beaucoup plus passif de l'ensemble des membres syndiqués, leur a permis d'influencer les positions et les stratégies des centrales syndicales, du moins de s'y faire entendre et de susciter des débats, particulièrement entre 1975 et 1980. Notre recherche sur cet aspect du militantisme syndical des marxistes-léninistes québécois éclaire des zones d'ombre de l'histoire politique récente de la province. De plus, cette étude amène une connaissance plus profonde de la place du radicalisme dans la culture politique québécoise et une meilleure compréhension du militantisme et de ses rouages. Afin d'atteindre nos objectifs, nous analysons d'abord le discours des marxistes-léninistes au sujet du monde syndical. Il sera notamment question des critiques sévères lancées contre les chefs syndicaux, ainsi que de la lutte idéologique qui secoue les différents groupes marxistes. Nous étudions ensuite les stratégies et les actions des m-l face aux syndicats, comme la volonté de se présenter à des postes électifs. Finalement, ce mémoire tente de mettre en lumière le militantisme m-l dans les différentes instances de la Confédération des syndicats nationaux, tout particulièrement le Conseil central de Montréal.

Trouble in Our Fields: Health and Human Rights Among Mexican and Caribbean Migrant Farm Workers in Canada - McLaughlin, Janet (University of Toronto, 2009)
For many years Canada has quietly rationalized importing temporary "low-skilled" migrant labour through managed migration programs to appease industries desiring cheap and flexible labour while avoiding extending citizenship rights to the workers. In an era of international human rights and global competitive markets, the Canadian Seasonal Agricultural Workers Program (SAWP) is often hailed as a "model" and "win-win" solution to migration and labour dilemmas, providing employers with a healthy, just-intime labour force and workers with various protections such as local labour standards, health care, and compensation. Tracing migrant workers' lives between Jamaica, Mexico and Canada (with a focus on Ontario's Niagara Region), this thesis assesses how their structural vulnerability as non-citizens effectively excludes them from many of the rights and norms otherwise expected in Canada. It analyzes how these exclusions are rationalized as permanent "exceptions" to the normal legal, social and political order, and how these infringements affect workers' lives, rights, and health. Employing critical medical anthropology, workers' health concerns are used as a lens through which to understand and explore the deeper "pathologies of power" and moral contradictions which underlie this system. Particular areas of focus include workers' occupational, sexual and reproductive, and mental and emotional health, as well as an assessment of their access to health care and compensation in Canada, Mexico and Jamaica. Working amidst perilous and demanding conditions, in communities where they remain socially and politically excluded, migrant workers in practice remain largely unprotected and their entitlements hard to secure, an enduring indictment of their exclusion from Canada's "imagined community." Yet the dynamics of this equation may be changing in light of the recent rise in social and political movements, in which citizenship and related rights have become subject to contestation and redefinition. In analyzing the various dynamics which underlie transnational migration, limit or extend migrants' rights, and influence the health of migrants across borders, this thesis explores crucial relationships between these themes. Further work is needed to measure these ongoing changes, and to address the myriad health concerns of migrants as they live and work across national borders.
Keywords: Canada; Caribbean; Farmworkers; Health; Health and environmental sciences; Human rights; Jamaica; Medical anthropology; Mexico; Migrant farm workers; Migrant workers; Migration; Seasonal Agricultural Workers Program; Social sciences; Temporary foreign workers; occupational health

State Strategy for Migration Management: Canada's Two Temporary Foreign Worker Programs, The Seasonal Agricultural Workers Program & The Live-in Caregiver Program - Reed, Austina J. (McMaster University, 2009)
This study applies an IPE approach to examine the economic conditions, motivations and interests which have driven the Canadian government and two sending countries, Mexico and the Philippines, to accept the terms and conditions of a regulatory framework encouraging short-term labour migration between them. The features of program development which underpin the Seasonal Agricultural Workers Program (SAWP) and the Live-in Caregiver Program (LCP) have not been compared side by side. Nor have the two programs been compared for the relationship that has developed over the years between the Canadian government and the two sending governments of Mexico and the Philippines. The study's core research question asks how the process of regulating cross-border labour migration works and how it is coordinated between two or more governments that form part of a migration system. An important research finding that emerges from the comparison is the categorization of different types of migration systems. I argue that the SAWP and LCP differ in how they are administered because relations between the various actors differ. Furthermore, what defines these relationships is the set of geopolitical and economic interests that each government carries when it negotiates the regulation of cross-border labour migration. Findings suggest that the geopolitical and economic imperative which has driven the SAWP's development is not the same for the LCP.

Collective Bargaining for New Brunswick Nurses by New Brunswick Nurses 1965-1969: In Unity There Is Strength - Reeves, Roxanne (University of New Brunswick, 2009)
New Brunswick nursing history is a little-known but significant story, and it helps us to understand women's paid work and how women organized to protect their interests in this occupation. While the profession's history demonstrates the importance of professional ideals, the New Brunswick, case also illuminates the struggle between these ideals and nurses' growing sense of dissatisfaction with wages and working conditions. In the mid-1960s in New Brunswick as elsewhere in Canada, nurses began to explore collective bargaining as a solution to poor wages and conditions and as a means to express concern for deteriorating patient care. This study examines the early stages of unionization among New Brunswick hospital nurses in 1965-1969. The evidence for this study is drawn from archival collections, interviews, newspapers, journals and secondary sources. Particular emphasis is placed on the pioneering efforts of the Social and Economic Welfare Committee (SEWC) of the New Brunswick Association of Registered Nurses (NBARN) and their efforts to educate members, lobby government, obtain outside expert advice and generally guide nurses towards a sense of collective identity that fostered a willingness to take collective action. By the end of the decade, nurses were included in a new Public Service Labour Relations Act, an outcome of the Royal Commission on Employer-Employee Relations in the Public Services (known as the Frankel Commission) which, among other features, greatly expanded the civil service and consequently the number of government employees with collective bargaining rights. Despite the fact that the new PSLRA had not yet been proclaimed, nurses in mid-1969 negotiated their first (if unofficial) collective agreement using the tactic of mass resignation to force a settlement. This thesis places the NBARN's early explorations of collective bargaining in the context of the political, economic and labour landscape of the 1960s.
Keywords: Health and environmental sciences; Social sciences

From Acculturation to Integration: The Political Participation of Montreal's Italian-Canadian Community in a Urban Context, 1945-1990 - Ricci, Amanda (Université de Montréal, 2009)
This thesis explores the political participation of the Montreal ltalian-Canadian community in an urban context, from 1945-1990. Concentrating on the local level, it examines the ltalian-Canadian contribution to municipal politics, the Quebec labour movement, mobilization with regards to the language debate, and' feminist activism. This historical account relies mainly upon the Montreal-based, Italian-language newspaper, Il Cittadino Canadese, as well as papers published by Italian-Canadian community organizations. The first chapter exammes the role ltalian immigrant elites played in the construction of a politicized ltalian-Canadian identity, as well as the establishment of numerous community institutions in the city. As a result of their efforts, several politicians of ltalian descent were elected to municipal government. Addressing the 1960 to 1977 years, the second chapter investigates the ltalian-Canadian contribution to Quebec's labour movement and language debate. Provoking the unification of the collectivity's institutions, the linguistic conflict solidified the Italian-Canadian identity, while it, also, paradoxically, led to internaI dissent and political heterogeneity amongst community members. The focus of Chapter 3, ltalian-Canadian feminist activism illustrates another form of political schism, when' a group of young students came together in 1978 to found the Centra Donne Italiane. Disassociated from the collectivity's mainstream institutions, ltalian feminists formed their own community,equally as politicized. As this thesis concludes, though originating with the language debate of the1960s and 1970s, the political heterogeneity present amongst Italian immigrants only heightened with time. With their basic needs met and a reasonable level of integration attained, Italian-Canadians, could afford both literally and figuratively, to distance themselves from the established cominunity leadership.
http://www.collectionscanada.gc.ca/obj/thesescanada/vol2/QMU/TC-QMU-7689.pdf

The Gendered Working of Class in Postindustrial, Service Sector Capitalism: The Emergence and Evolution of the British Columbia Nurses Union, 1976-1992. - Roth, Mark Andreas (Simon Fraser University, 2009)
This thesis explores the emergence and initial evolution of the British Columbia Nurses Union from 1976 to 1992. The thesis argues that class and gender framed interrelated processes of organizational change, labour action, and political consciousness for British Columbia’s nurses. These changes took place in the context of a historical struggle between professionalism and trade unionism in nursing, and during a turbulent and transformative era for western capitalism and the role of the capitalist state in the 1970s and 1980s. This thesis argues that class, as a socioeconomic relationship and as lived experience, was the driving force behind organizational, economic, and political change in the nursing occupation. This central assertion stands in sharp contrast to claims that class has ceased to be of socioeconomic or political importance in postindustrial, capitalist society.

A Study of the English Teachers’ Association of British Columbia, 1959-2000 - Saltel, Lonny Darlene (Simon Fraser University, 2009)
This study traces the efforts of British Columbia teachers as they endeavour to have increasing input into the educational policies of the Department of Education. It is grounded in a study of primary archival records and written in the form of an historical narrative. Primarily, I focus on the English Teachers' Association in B.C.: I trace its growth as a professional organization and follow its increasingly strident attempts to address the growing professional interests of English/Language Arts teachers in response to government policies, especially those affecting curriculum. Three main interrelated themes permeate the study: the professionalization of B.C. English/Language Arts teachers, the growth in the political power of teacher associations in B.C., and the effects of the B.C. government's changing educational policies in English/Language Arts classrooms. My study follows the English teachers' association from its beginning in 1959 when it was known as S.A.T.E., the Secondary Association of Teachers of English; during the years of 1971-1994 when it was called B.C.E.T.A. , the British Columbia English Teachers' Association; to its later years as B.C.T.E.L.A., the British Columbia Teachers of Engli sh Language Arts. The study reveals that as the decades pass, the association becomes increasingly persistent in its efforts not only to further the professional interests of English teachers but al so to provide input to the government on curricular decisions affecting Engli sh/Language Arts classrooms. It al so becomes increasingly persistent in its dealings with the government as their philosophies of education become more diverse.

Organizing the Unorganized: The Service, Office, and Retail Workers' Union of Canada (SORWUC), 1972-1986 - Smith, Julia Maureen (Simon Fraser University, 2009)
This thesis examines the Service, Office, and Retail Workers' Union of Canada (SORWUC), an independent, grassroots, socialist feminist union that organized unorganized workers in Canada in the 1970s and 1980s. It looks at SORWUC's role in Canadian labour history in general, and its efforts to organize unorganized workers in particular, focusing on SORWUC's efforts to organize workers at a pub and a restaurant in British Columbia. The central thesis of this work is that SORWUC's socialist feminist unionism and commitment to organizing unorganized workers positioned the union as radically different from much of the 1970s Canadian labour movement, and that this difference both helped and hindered the union in its efforts to organize the unorganized. By examining SORWUC from this neglected perspective, this thesis ultimately aims to demonstrate SORWUC's importance to the historiography of class and labour organizing in Canada.
https://cha-shc.ca/prize-winner/julia-maureen-smith/
Keywords: British Columbia; Canada; Labour Organizing; Labour Unions; Service Industry; Service; Office; and Retail Workers’ Union of Canada (SORWUC); Socialist Feminism

For Liberty, Bread, and Love: Annie Buller, Beckie Buhay, and the Forging of Communist Militant Femininity in Canada, 1918-1939 - Toews, Anne Frances (Simon Fraser University, 2009)
During the interwar years, friends Annie Buller and Beckie Buhay established careers with the Communist Party of Canada and forged a uniquely Communist militant femininity that led to their eventual canonization by the Party as ideal comrades. Using a biographical approach to women’s working-class history, this thesis examines these women’s significant contributions to the CPC’s political project as gendered work. It also demonstrates that although their representation of themselves as comrades was organized around their understanding of themselves as workers, it was shaped too by particularities of ethnicity, gender, and other factors that were all subsumed in the Party’s egalitarian rhetoric. Additionally, in exploring how their lifelong friendship supported their construction of Communist militant femininity, and thus enabled their work, this thesis contributes to a developing historiography of friendship that focusses on its work rather than its nature, and that is inclusive of the friendships of working-class women.
Keywords: Friendship; Labour College; communist; comrade; militant; woman question

Depression on the Frontline: An Examination of the Impact of Working Conditions and Life Stressors on Sex Workers, Stylists and Servers - Vallance, Katherine Jane (Victoria, 2009)
Changes to the global economy over the past few decades along with growing support for neo-liberal policies in Canada have led to an increase in precarious, low-wage frontline service work. These kinds of occupations often involve sustained interaction with clients and have high job demands, low job control and insufficient monetary reward. Further, many of these jobs also tend to be gendered (i.e., they involve a large degree of ‘emotional’ labour or care work that is predominantly carried out by female workers). Working conditions such as these can have a negative impact on the mental health of frontline service workers leading to psychological distress and depression. Chronic stress or cumulative stressful life events can also increase vulnerability to depression. While these stressors can be exacerbated by poor working conditions, they can also exist independently of them. Comparative research across two or more frontline service occupations, similar in broad strokes but differing in workplace characteristics, is especially needed to understand how structural and contextual factors in the workplace and over the life course interact to produce depression. This thesis presents data from my supervisor (Dr. Cecilia Benoit) and colleagues’ 4-wave longitudinal study entitled “Interactive service workers’ occupational health and safety and access to health services” (Benoit, Jansson, Leadbeater & McCarthy, 2005). This is a study of three types of frontline service jobs – two in the formal economy (hairstyling and food and beverage service) and one in the shadow/informal economy (sex industry). Results of this secondary analysis demonstrate that not only do working conditions have a significant impact on the mental health of frontline service workers but that stressful life events also have very strong explanatory power in understanding why certain workers experience depression more than others. The findings indicate that sex workers have the highest levels of depression, in comparison to stylists and servers. Yet sex workers report protective factors in their jobs, including higher comparative decision latitude, that contradict much of the current literature on sex work. The thesis concludes with policy recommendations and gives direction for further research in the area of frontline service work and depression.

Stories of Unionization: Four Teachers' Perspectives on Collective Bargaining in Two Canadian Private ESL Schools - Breshears, Sherry Diane (Simon Fraser University, 2008)
The private English language training industry in Canada has grown rapidly in recent years. While subject to influences of market competition, ESL schools have had little educational or labour regulation. This study presents life history interviews with four teachers who became involved in forming unions at their workplaces because of their experiences with just labour practices. The findings show that teachers sought union protection to deal with a pervasive sense of insecurity in their jobs. Through unions, they established clearer processes for dealing with such issues as the allocation of work and the resolution of grievances, a forum for communicating concerns to management, and a peer support structure. Additionally, these teachers have gained significant increases in salary and benefits. These narratives also show teachers, both individually and collectively, engaging in resistance as they confront the daily infringement of business priorities on their capacities to develop and practice as educators.

Watching Workers: A Critical Review of the Law Regarding Electronic Employee Monitoring in Non-Unionized Workplaces in Canada - Bueckert, Melanie R. (University of Manitoba, 2008)
This thesis addresses the topic of electronic employee monitoring in non-unionized workplaces in Canada. Electronic employee monitoring is defined as including (1) the use of electronic devices to review and evaluate employees’ performance; (2) ‘electronic surveillance’; and (3) employers’ use of computer forensics. Detailed consideration is given to a variety of technologies, including computer, internet and e-mail monitoring, location awareness technologies (such as global positioning systems and radio frequency identification), as well as biometrics, and the developing case law surrounding these innovations. Analogies are drawn to the jurisprudence developing with respect to unionized workplaces and under statutory unjust dismissal regimes. This analysis leads to the conclusion that legislative reform is necessary, either through(1) the creation of parallel private sector privacy regimes, such as those in British Columbia and Alberta, mirroring existing federal legislation; (2) amendments to existing employment standards legislation; or (3) the enactment of a stand-alone surveillance statute.

Commissioning Consent: An Investigation of the Royal Commission on the Relations of Labour and Capital, 1886-1889 - Cole, Stephen J. (Queen's University, 2008)
The 1880s were turbulent years in the Dominion. Under the auspices of the National Policy, Canada was in the midst of a social and political ‘transformation.’ The social and cultural aspects of this transformation became a source of public debate as the ‘Labour Question’ and the relations between labour and capital reached a high mark of political and economic significance. Waves of strikes and the emergence of large international labour organizations challenged many liberal Victorian ideas about a strictly limited state. Many looked upon the federal government as responsible not only for economic growth, but also for protection from the more pressing problems of industrial life. The Royal Commission on the Relations of Capital and Labour is a testament to not only the turbulent economic relations in late-Victorian Canada, but the emergence of the Canadian state’s active role in social relations. Its very title envisioned a dual role for the Canadian state: to “promote the material, social, intellectual and moral prosperity” of labouring men and women, and to improve and develop “the productive industries of the Dominion so as to advance and improve the trade and commerce of Canada.” However, this thesis argues that the Labour Commission was more subtly designed to enhance the prestige of the Canadian state and install Ottawa as an authority on, and mediator of, industrial relations in Canada. Attention to the formation, activities, and impact of the Labour Commission suggests that, rather than an exercise in addressing a mounting social polarization between “labour” and “capital,” the Commission lends insight into the emergence of a Canadian middle class. It was a carefully-constructed exercise in the assertion of middle-class cultural hegemony whereby such values and understandings as respectability, morality, manliness, worth and expertise were naturalized. In the process, the tension between labour and capital was diminished and in its place were developed visions of social reciprocity and mutual interest. It is in this way that the Labour Commission was an exercise in ‘commissioning consent:’ it placed oppositional voices and wrenching exposés about industrial life in a framework that worked to quell rather than stimulate far-reaching critiques of the established order. The Commission’s formation, methodology and language functioned like an industrial exhibition rather than a pointed social investigation. The evidence presents a thriving economy that had grown exponentially under a wise and paternal government. It also presented a vision of the Dominion whereby the disturbances that occurred between labour and capital could be handled within a conventional language of liberal politics. In addition, social and intellectual elites were fully ensconced in the formation and legitimization of these social and moral understandings. Because it was up to the state to select who would speak for labour and capital, the Commission’s message was not one of class polarization. Thus, exploring who became ‘labour’ and who ‘capital,’ and what sorts of things they said to each other, sheds light on to the emergent strategies of the Canadian state as it sought to understand and influence civil society. The Commission is an indication, even anticipation, of a more activist and energetic state.

Precariousness on the Menu: Restaurant Work and Labour Mobility Within the Low-Wage Service Industry in Kingston, Ontario - Denstedt, Mark James (Queen's University, 2008)
Precarious employment refers to forms of work characterized by limited job security, few employment benefits, lack of control over the labour process and low-wages. Restaurant work demonstrates a range of precarious forms of employment and reveals the complexity of issues that such jobs raise in the context of the regulation of the local labour market. This thesis analyses the nature of precarious employment in the restaurant industry in Kingston, Ontario. In particular, it seeks to understand how precarious employment is shaped by the structure and dynamics of the local labour market. The research highlights the role played by labour mobility, in shaping workers’ experiences of precarious work. Labour mobility refers to the movement of workers between different jobs and between different worksites within a structured local labour market as they seek to better their economic situation and generate a sustainable income for themselves. Through a discussion of labour mobility, this thesis seeks to contribute to a new lens through which the impacts of a precarious and flexible labour market can be better understood as they shape the lives of workers themselves. The objective of this study is to better understand the factors which shape the lived realities of precarious restaurant workers in one specific local labour market. The empirical analysis draws on data collected by Statistics Canada and interviews conducted with both employers and employees in local restaurants to analyze the structure of the local labour market and the nature of precarious employment. The research demonstrates that the restaurant industry in Kingston is comprised of three distinct submarkets, each of which appears to operate largely independently of one another. Interviews were conducted with employees and employers in the submarket located in downtown Kingston. Within this submarket the combined processes of labour market segmentation and labour mobility has a significant impact on workers experiences of precarious employment. By understanding the complex interaction of these two features within the labour market, we can begin to conceive of ways to address the issues associated with the precariously employed in the low-wage service industry.

A Crisis of Social Democracy: Organized Labour and the NDP in an Era of Neoliberalism - Fowler, Tim (Brock University, 2008)
The NDP was founded out of the ashes of the Co-Operative Commonwealth Federation to cooperate with the Canadian Labour Congress to become the 'political arm of organized labour' in Canada. The NDP has long claimed they are the party which represents the policy goals of organized labour in Canada: that the NDP alone will fight for trade union rights, and will fight for Canadian workers. Divergent Paths is an examination of the links between the labour movement and the NDP in an era ofneo-liberalism. Provincial NDP governments have become increasingly neoliberal in their ideological orientation, and have often proved to be no friend to the labour movement when they hold office. The Federal party has never held power, nor have they ever formed the Official Opposition. This thesis charts the progress of the federal NDP as they become more neoliberal from 1988 to 2006, and shows how this trend effects the links between the NDP and labour. Divergent Paths studies each federal election from 1988 to 2006, looking at the interactions between Labour and the NDP during these elections. Elections provide critical junctions to study discourse - party platforms, speeches, and other official documents can be used to examine discourse. Extensive newspaper searches were used to follow campaign events and policy speeches. Studying the party's discourse can be used to determine the ideological orientation of the party itself: the fact that the party's discourse has become neoliberal is a sure sign that the party itself is neoliberal. The NDP continues to drive towards the centre of the political spectrum in an attempt to gain multi-class support. The NDP seems more interested in gaining seats at any cost, rather then promoting the agenda of Labour. As the party attempts to open up to more multi-class support, Labour becomes increasingly marginalised in the party. A rift which arguably started well before the 1988 election was exacerbated during that election; labour encouraged the NDP to campaign solely on the issue of Free Trade, and the NDP did not. The 1993 election saw the rift between the two grow even further as the Federal NDP suffered major blowbacks from the actions of the Ontario NDP. The 1997 and 2000 elections saw the NDP make a deliberate move to the centre of the political spectrum which increasingly marginalised labour. In the 2004 election, Jack Layton made no attempt to move the party back to the left; and in 2006 the link between labour and the NDP was perhaps irreparably damaged when the CAW endorsed the Liberal party in a strategic voting strategy, and the CLC did not endorse the NDP. The NDP is no longer a reliable ally of organized labour. The Canadian labour movement must decide whether the NDP can be 'salvaged' or if the labour movement should end their alliance with the NDP and engage in a new political project.
Keywords: Social sciences

Racialized Immigrants In Canada’s Changing Labour Market: An Investigation Of The Effects Of Precarious Work On Black Caribbean Women - Hibbert, Maqueita (Ryerson University, 2008)
This research undertakes an examination of the employment opportunities and experiences of black Caribbean women in Canada, particularly within the context of the growing trend towards precarious jobs—casual, part-time and low paying—in the restructured Canadian labour market. The specific purview of this study is the labour history and employment experience of a representative group of black Caribbean women who work as Personal Support Workers in nursing homes across the Greater Toronto Area. A main concern of the study is to understand the ways in which precarious work affects these women’s settlement and integration experiences, particularly their ability to gain economic independence; this, in turn, affects a number of variables related to their, and others, perception regarding their status and place in Canada. By focusing on the case of Personal Support Workers, the study aims to shed light not only on the employment experiences of black Caribbean women in this sector but also to examine more closely the policies and employment practices that create labour market “niches” or labour “segregation” along racial and gender lines.

The Homeless and Reformers: Negotiating Progress in the Upper Streets of Halifax, 1890–1914 - Hood, David (Carleton University, 2008)
The extremely poor have often been cast as deviants or others, in both the past and the present. Historians of Atlantic Canada have used the idea of deviance as an acceptable approach to the poor and homeless of the past and tacitly encourage us to see the contemporary homeless as deviants. Victorian theorists such as Malthus and Mayhew pejoratively characterized the poor as an underclass. Contemporary writers have provided evidence that challenges the use of the concept in Canada. But it remains a powerful force within American sociology, which is able to cast its influence over Canadian historical writing. It is the contention of this research that it is possible to be true to the past, to reflect the warts and downfalls of the extremely poor and homeless who lived there, but at the same time recognize their efforts to follow prevailing norms and to empathize with their plight and in doing so generate at least the possibility of recognition and empathy in the present. Such recognition and empathy may be the keys to creating and maintaining humane solutions to poverty and homelessness. The examinations conducted by this research address an area of our past that has been largely overlooked. This research supplements broad historical surveys of social welfare legislation by examining social welfare policy in action at the local level. By positioning itself at the convergence of labour history and studies of poverty, and by demonstrating that the populations examined by these discrete areas of research are more alike than different, this research shows that labour history can be extended to include many of those who lived "rough" in the past. Through its approach this research hopes to encourage a view that can help to integrate the study of extreme poverty and homelessness into the mainstream of Canadian historiography.
Keywords: Halifax; Homeless; Nova Scotia; Progress; Reformers; Social sciences

When Red Meets Green: Perceptions of Environmental Change in the B.C. Communist Left, 1937-1978 - Martin, Eryk (University of Victoria, 2008)
From the 1940s to the 1970s the communist left in British Columbia used debates and perceptions of environmental change as a means to engage in a critique of capitalist society. In engaging in these debates, communists articulated a Marxist understanding of the connections between capitalism and environmental change. However, these articulations were heavily connected to broader occurrences that situated the communist left alongside a diverse group of social actors. Beginning in the 1940s the communist left situated their critique of provincial forest policy into a wider social debate over the management of forest resources. During the 1950s and 1960s, concerns over environmental change were transformed into debates over the effects of nuclear weapons and industrial pollution. From the late 1960s through to late 1970s elements of the communist left once again engaged with the environmental changes taking place in the forest sector, as renewed concerns developed over the status of the forest economy and the preservation of wilderness areas. To investigate the communist left’s perceptions and politicization of these issues this thesis focuses on the activities of communist controlled unions such as the International Woodworkers of America as well as the B.C. section of the Communist Party of Canada/Labour Progressive Party. In addition to these organizations, this thesis also follows the experiences of Erni Knott. As a woodworker, a founding member of the IWA, a member of the Communist Party, and an active environmentalist, Knott’s experiences highlight the complex way in which communist politics merged and conflicted with perceptions of environmental change.

Rural Businesses on Vancouver Island: Challenges and Opportunities - Siemens, Lynne Marie (University of Hertfordshire, 2008)
Many rural areas are undergoing structural changes as jobs in forestry, fishing, mining, agricultural and other natural resource-based industries decline. These communities, often based around these industries, are generally small and located some distance from urban areas. They are faced with decreasing population as residents and their families leave for jobs elsewhere. As a result, the communities and residents are looking for alternative ways to create employment and sustain themselves. Given the nature of these rural locations, many small businesses based there face challenges that are not generally experienced by enterprises in urban areas. Some communities are not accessible by paved road while others are not accessible by road at all, relying instead on water and air transportation. The business people in these areas often operate without standard business infrastructure, which can include telephone lines, broadband Internet, banking services and other items, and can have difficulty accessing supplies, customers, employees and other required materials. However, there has been relatively little research on the challenges facing rural businesses and the specific methods by which these owners mitigate these challenges. Understanding and addressing the challenges faced by these businesses becomes important in order to support and encourage economic growth and development in these rural communities. Building on this context, this research looks to answer the following questions: • Why do people start businesses in rural locations? • What type of businesses do they start? • What challenges do these rural businesses face? • How do owners respond to these challenges? Vancouver Island and the surrounding smaller islands in British Columbia, Canada serve as the research site. Given the exploratory nature of this research, an inductive approach has been selected with the use of case studies, interviews and grounded theory analysis. Purposeful sampling is used with the sample businesses meeting specific criteria, based on location, business size and definition of success. These businesses are interviewed at their locations to allow the researcher to experience the challenges associated with accessing the particular rural community. The interview topics are focused on the above research questions. There are several common characteristics among the sample owners and their businesses. The owners tend to be in-migrants who moved to the rural area for lifestyle reasons. They have started their business to provide an income, take advantage of a business opportunity, or both. Family members, particularly spouses, are actively involved in the business. In many cases, participants supplement their business income with other income sources to ensure business viability. Success is measured generally by personal and lifestyle goals, rather than financial criteria. The businesses face common challenges in terms of a limited local population base which impacts on market size and labour pool, rural location and access to urban centres, gaps in business and social services infrastructure and heavy time demands. The owners respond to these challenges in a variety of ways which includes the involvement of family, core business diversification, alternative income sources, long hours invested in the business and involvement with the community. To meet these challenges and devise their responses, the owners draw upon four key resources – their own skills and attitudes, their family, business and community. The resulting conceptual framework draws together these key resources and suggests that all four must be present to ensure success within a rural context. Each resource is comprised of several components which contribute to business success. The framework also integrates several resource-based theories, which consider the key resources either separately or in pairs, to create a holistic model. The conclusions focus on several key areas. This research contributes to the knowledge base on rural small businesses by creating a framework that draws directly from the experience of these owners and their objectives and motivations for their businesses. It reflects their internal focus and a concentration of the four resources that they access easily from within their domain. This research also suggests some possible roles for government which focus on its role in shaping the larger environment, particularly at the infrastructure level and human capital development. Finally, future research directions are recommended. This study considers a relatively unexplored topic and suggests ways for rural small businesses to address the challenges which they face. With this knowledge, individuals, businesses, communities and other interested organizations can work to achieve their economic development goals.

Les travailleurs miniers de l'Abitibi-Témiscamingue : la main-d'oeuvre de la mine Lamaque, 1948-1985 - Simard, David (Université de Montréal, 2008)
Ce mémoire porte sur les travailleurs de la mine Lamaque entre 1948 et 1985. À partir d’une étude approfondie des fichiers d’employés de l’entreprise, qui est l’une des plus riches mines d’or de l’histoire du Québec, nous analysons l’évolution de la main- d’œuvre sous les volets de la composition ethnique, de l’expérience dans le secteur minier ainsi que de la mobilité. Notre enquête révèle l’existence de deux périodes-clés autour desquelles on assiste à une transformation rapide de la main-d’œuvre: la période 1948-1960 est le théâtre d’un important processus d’homogénéisation des effectifs alors que les années 1967-1977 sont la scène d’un double processus de sédentarisation et de qualification de la main-d’œuvre. D’un groupe de travailleurs cosmopolites, peu expérimentés et très mobiles, il en ressort, au sortir de ces années, une main-d’œuvre nettement plus expérimentée, plus sédentaire et composée presque exclusivement de travailleurs canadien-français et, de surcroît, témiscabitibiens. Au-delà de ces transformations, notre mémoire comporte un bref aperçu de l’histoire de l’industrie aurifère québécoise et de la mine Lamaque, du « boom minier » des années 1930 à la grande relance de l’industrie au début des années 1980. De plus, nous portons une attention particulière aux travailleurs d’origine européenne qui forment, jusqu’à la fin des années 1960, une proportion appréciable de la main-d’œuvre. En plus de lever le voile sur la composition de ce groupe de travailleurs, notre étude révèle des similitudes insoupçonnées entre le contingent européen et canadien-français.
https://doi.org/1866/7681

Co-Opting Precariousness: Can Worker Cooperatives Be Alternatives to Precarious Employment for Marginalized Populations? A Case Study of Immigrant and Refugee Worker Cooperatives in Canada - Wilson, Amanda (McMaster University, 2008)
This thesis is an exploration into the potential for worker cooperatives to be conceptualized and experienced as an alternative to precarious employment for immigrants and refugees. It argues that current analysis and responses to precarious employment fail to fully address the root causes of precarious employment and fail to suggest what forms of alternative employment relations we should be striving to build. It is argued that by tracing the roots of precarious employment to the organization of work, the worker cooperative model can be seen as a potential solution to these root problems. This hypothesis is explored through two case studies of immigrant worker cooperatives, analyzing the employment experiences of several of its members. It concludes that workers cooperatives appear to provide alternatives in the areas of control, security and social capital and empowerment. However, more work is needed to support and facilitate the development and sustainability of cooperatives in order to improve in the areas of wages and formal benefits. Despite the challenges of worker cooperatives, the author argues that they remain an important tool, invoking a politics of the act that seeks to build alternative spaces of employment without relying on government or employers.

Workability of Intergovernmental Administrative Relations: A Comparison of Labour Market Policy in Post-Devolution Canada and the United Kingdom - Wood, Donna (University of Edinburgh, 2008)
This is a comparative study of intergovernmental relations in labour market policy in Canada and the United Kingdom (UK) between 1996 and 2006, the first phase of devolution in each country. The study focuses primarily on relations between the central government and a single sub-state in each country (Alberta in Canada and Scotland in the UK) and addresses three research questions: 1) to what extent were there differences in intergovernmental relations between the countries?2) what accounted for these differences? 3) what impact did these differences have on the character and workability of the intergovernmental relations system in each country? Workability was assessed based upon the degree to which trust ties developed between senior officials. The analysis concludes that the structure of the state, the structure of the policy domain, and the presence of two important accommodation mechanisms in the UK not found in Canada (the party system and the civil service) made intergovernmental relations in labour market policy in the two countries fundamentally different. In Canada, intergovernmental relations were multilateral, interprovincial and bilateral, whereas in the United Kingdom they were only bilateral. Despite devolution, the UK Government retained control of most policy levers, whereas in Canada devolution has limited federal control and influence and any notion of a national labour market system. Trust ties were enhanced by consistency between the key players, routinized engagement, reliability, honesty, respect, capacity and willingness to engage, and transparency. Although shared objectives made engagement easier, they were not a prerequisite for a positive relationship. Bilateral relationships that took place within the geographic boundaries of Alberta and Scotland were considered as positive and highly workable. Difficulties arose when relationships became multilateral or bilateral relations were managed at a distance. Despite devolution, multilateral relations in the historically conflicted labour market policy domain in Canada remained competitive, with a low degree of workability. Relationships with respect to disability and immigration issues were more positive. In the UK relationships in the welfare to work policy area were cooperative and highly workable. Relationships in skills and immigration did not fare as positively.

Skilled Trades' Work and Apprentice Training in the Manufacturing Industry with a Primary Focus on the Millwright Trade: An Inter-Generational Study - Wren, John Charles (University of Toronto, Ontario Institute for Studies in Education, 2008)
Technology has enabled management to utilize automation in the methods of production, and as such promoted a reduction in the use of traditional skills for traditional skilled trades' workers while narrower task specific apprenticeship training programmes promote the loss of trade knowledge traditionally passed from a trades' person to an apprentice in the manufacturing industry. The purpose of this intergenerational study is to trace the changing skill requirements affected by developing technologies in the manufacturing process focusing on the traditional skills of millwright trade, and associated skilled trades. To place in context the origins of the skilled trades' I have included brief histories of five skilled trades, to represent a selection of skilled trades' often closely connected through their work in the manufacturing industry; the millwright, electrician, welder, toolmaker and machinist. In an effort to also report the possible effects of technology on skilled trade labour from a tradesperson's perspective I have utilised my own experiences and incorporated anecdotal evidence from interviews with certified millwrights and apprentices that are either presently working in the trade, or have retired from the trade in Canada. Interviews with three generations of millwrights assisted in making comparisons of training and expectations of millwright work, together with changes in the control millwrights' exercise over the jobs they perform. The focus of the thesis is the possible effects of technological progress on the required skill sets of three generations skilled trades' with a primary focus on millwright skilled trades'. Restructuring and the utilization of new technologies has facilitated a reduction in the overall number of skilled trades' workers that were previously required when traditional skilled trades' personnel were utilised. Therefore, utilization of technology to lower production costs by modern industry is affecting social structure, in that, traditional opportunities for members of the working class, without the benefit of a university education, are restricted in their ability to obtain well paid jobs as skilled trades' personnel in the manufacturing industry. Thesis: Technology has enabled automation to be utilized by management in the methods of production, and as such promoted a reduction in discretion and control in the use of traditional skills for traditional skilled trades' workers while narrower task specific apprenticeship training programmes promote the loss of trade knowledge traditionally passed from a trades' person to an apprentice in the manufacturing industry.
Keywords: Apprentice training; Education; Manufacturing; Millwright; Skilled trades

La perception de la fête internationale des travailleurs dans les journaux canadiens entre 1906 et 1945 - Zombecki, François (Université du Québec à Montréal, 2008)
Le 1er mai 1906, les membres d'un éphémère parti socialiste canadien organisent à Montréal la première célébration de la fête internationale des travailleurs. Des centaines de personnes y défilent sous le drapeau rouge. L'événement se répète ensuite presque chaque année, et s'étend à la plupart des grandes villes du pays. L'histoire du mouvement socialiste / communiste au Canada et au Québec a certes été écrite, mais l'historiographie délaisse le sujet de sa fête annuelle. Pourtant, les journaux canadiens ont couvert l'événement, année après année, léguant aux générations suivantes une riche couverture. Celle-ci représente un outil utile, bien qu'imparfait, pour mieux saisir l'opinion de la population de l'époque à l'endroit des communistes. La présente recherche analyse plus de 400 articles de grands quotidiens pour sonder la perception des Canadiens, durant la première moitié du XXe siècle, quant au phénomène de la fête du 1er mai et au mouvement socialiste / communiste qui l'anime. Dans un premier temps, nos recherches présentent la couverture des journaux de plusieurs grandes villes canadiennes. Nous constatons alors d'importantes différences entre la perception des Canadiens français et celle des Canadiens anglais au Québec. Nous découvrons également une affinité particulière à Winnipeg -et même à Vancouver, dans une moindre mesure -pour le mouvement et sa fête. Le facteur ethnique explique en bonne partie tant les affinités de certaines communautés pour le mouvement, que la répulsion des Canadiens français. Dans un deuxième temps, à travers une approche chronologique plutôt que régionale, des facteurs conjoncturels et internationaux expliquent les fluctuations dans le ton des journaux entre 1906 et 1945. Ce travail de recherche jette la lumière sur une fête particulière, exclue du calendrier officiel nord américain et pourtant observée à travers la majeure partie du monde occidental. L'analyse de la couverture journalistique de l'événement permet de tirer d'intéressantes conclusions quant à la façon dont a été perçu le mouvement communiste canadien, au moment de son apogée.

A Proletarian Prometheus: Socialism, Ethnicity, and Revolution at the Lakehead, 1900-1935 - Beaulieu, Michel S. (Queen's University, 2007)
[Analyzes] various socialist organizations operating at the Canadian Lakehead (comprised of the twin cities of Port Arthur and Fort William, Ontario, now the present-day City of Thunder Bay, and their vicinity) during the first 35 years of the twentieth century. It contends that the circumstances and actions of Lakehead labour, especially those related to ideology, ethnicity, and personality, worked simultaneously to empower and to fetter workers in their struggles against the shackles of capitalism. The twentieth-century Lakehead never lacked for a population of enthusiastic, energetic and talented left-wingers. Yet, throughout this period the movement never truly solidified and took hold. Socialist organizations, organizers and organs came and went, leaving behind them an enduring legacy, yet paradoxically the sum of their efforts was cumulatively less than the immense sacrifices and energies they had poured into them. Between 1900 and 1935, the region's working-class politics was shaped by the interaction of ideas drawn from the much larger North Atlantic socialist world with the particularities of Lakehead society and culture. International frameworks of analysis and activism were of necessity reshaped and revised in a local context in which ethnic divisions complicated and even undermined the class identities upon which so many radical dreams and ambitions rested.
https://qspace.library.queensu.ca/bitstream/1974/1715/1/Beaulieu_Michel_S_200712_PhD.pdf
Keywords: 1900-1935; Canada; Communist Party of Canada; Ethnicity; Finns in Canada; Fort William; Ontario; Industrial Workers of the World; Labour history; Lakehead; Northwestern Ontario; One Big Union; Port Arthur; Ontario; Radicalism; Revolution; Social Democratic Party of Canada; Socialism; Socialist Party of Canada; Winnipeg general strike

La domesticité dans la colonie laurentienne au XVIIe siècle et au début du XVIIIe siècle (1640-1710) - Bessière, Arnaud (Université du Québec à Montréal et Université Paris IV - Sorbonne, 2007)
Cette thèse porte sur les domestiques au Canada entre 1640 et 1710. Recrutée en France ou dans la colonie, cette main-d'oeuvre, principalement masculine, est au service des paysans propriétaires et des communautés religieuses. Ses fonctions sont donc surtout liées à l'agriculture : défrichements, culture des terres, soin du bétail. Mais cela n'exclut pas des tâches comme le soin des malades et l'entretien ménager pour les communautés religieuses et les employeurs urbains plus fortunés. Au fil des ans, la composition du groupe se modifie : les domestiques sont de plus en plus d'origine canadienne et de plus en plus jeunes. Cette évolution est certes à rapprocher de la baisse du mouvement migratoire vers la colonie qui était en grande partie formé de domestiques. En plus d'analyser les modalités d'embauché, la thèse aborde la question des relations entre les maîtres et les domestiques et tente de cerner le devenir social du groupe dans la colonie.
https://cha-shc.ca/prize-winner/arnaud-bessiere/
Keywords: Canada; Domesticité; Domestique; Employeur; Engagé; Immigration; Main-d'œuvre; Maître; Nouvelle-France; Salaire; Servante; Serviteur; XVIIe siècle.

British Juvenile Immigrants in Canada 1868 to 1939: A Study of the Relationship Between Societal Changes and the Treatment of Home Children - Coombes, Brianna Leigh (Ryerson University, 2007)
This paper examines the history of the British juvenile immigrants, a group of over 100,000 children who arrived in Canada between 1868 and 1939 to work on farms or as domestic workers. There was both a pressing need within Canada for farm workers, and overcrowding in British cities, therefore conditions were right for a mutually beneficial labour exchange between the two nations. British philanthropists encouraged this movement and ensured its continued success over a seventy year period. The societal changes that occurred in Canada during the same period as a result of the reform movement are also traced within this historical examination. The increase in child welfare policies, and the subsequent attitudinal changes in the Canadian public also impacted how the home children were treated and viewed. Through this research, this neglected group of immigrants will be given a more prominent position in Canadian social and immigration history.

Chameleons, Chimeras and Shape-Shifters: The Production of Neoliberal Government in Ontario - Coulter, Kendra (University of Toronto, 2007)
Drawing on data from a sixteen-month ethnography of Queen’s Park, the provincial legislature of Ontario, this study analyses and critiques the evolving production of neoliberal government. The work of real social actors, primarily political workers and politicians, and their active ideological and material creation of government, is central to my focus on the neoliberal project of the Liberal government in Ontario. After charting the historical trajectory of neoliberalism internationally and in Canada, with a particular emphasis on the Third Way approach, Icentre on thedevelopment of neoliberal political culture and restructuring in Ontario. Then I provide an in-depth analysis of the production of the Liberal government, focusing on social and fiscal policies and policy-making, hegemonic gender and class politics, and political communications and spin. I conclude that, at one level, the Liberal chimera fused certain progressive practices and language with neoliberal policies and rhetoric. At the same time, significant and dangerous initiatives that interlocked the public and for-profit sector conceptually and materially were pursued. Thus, a more camouflaged form of deep neoliberal integration was produced.
OCLC: 664421107
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Labour Goes to War: The CIO, the People's War, and the Construction of a "New Social Order," Toronto, 1939-1945 - Cuthbertson, Wendy Elizabeth (University of Toronto, 2007)
The CIO related this narrative to working-class Canadians through new, union channels of communication and through a myriad of union-minded social interactions. Together - the CIO's narrative of victory and its subaltern public sphere that communicated this narrative - helped the CIO overcome formidable obstacles to organizing. The Canadian CIO's 1930s momentum had stalled by 1939, but by 1944 it was the country's largest labour organization and was influencing Canadian politics. Using union newspapers, organizing literature, minutes, correspondence, oral interviews, government and corporate records, and the daily press, this dissertation describes and analyzes how the CIO organized thousands of wartime workers into unions in spite of significant obstacles. This study then examines the institutions the CIO developed to create a union "mini-public sphere," where workers debated and developed union positions on issues facing them as workers, family members, citizens and military veterans. The CIO was successful in turning private, workplace issues such as union recognition and bargaining rights into public issues that government was forced to deal with, and its organizing successes and its entry into politics witnessed burgeoning support for the social democratic CCF, a phenomenon that encouraged mainstream political parties to adopt more progressive platforms. The CIO's breakthrough was based not just on worker-empowering wartime labour shortages. Its skill in using modern communications was also a factor in its wartime success, as well as its use of the war as a central character in these communications efforts. CIO communications used a narrative that elided workers with warriors as partners in a "people's war" to defeat the nation's enemies and build a new social order. The CIO told workers that if they organized into unions, they would have the power to shape a peace that, unlike after the Great War, would benefit this worker-warrior partnership. Victory was thus defined not merely as defeating the Axis but creating a modern, new Canada, where workers would have citizenship rights in the workplace and where citizenship entailed a fairer, more egalitarian society. The CIO's talk about rights extended to women workers, and its arguments for equal pay and women's seniority were increasingly based on women's human rights.

The Split in the AFL-CIO: Implications for the Canadian Labour Movement - Declerck, Sarah (McMaster University, 2007)
In July 2005, six unions withdrew from the central labour federation in the United States, the AFL-CIO. In September 2005, joined by a seventh union, the disaffiliated unions formed a rival labour federation called Change to Win (CTW). On the surface according to Stem, leader of the CTW coalition, what divides the two sides of the split is a disagreement over whether or not to place greater emphasis on organizing new members or altering the political climate in the US in order to facilitate orgamzmg. This thesis explores some of the earlier debates within the union renewal literature in the US and in Canada and exposes many ofthe similarities between the 1995 "New Voices" leadership ofthe AFL-CIO and the CTW leadership. Through a description and analysis of the events that led to the split in the AFL-CIO, the limitations ofthe debates that led to the split are revealed and the strategies for union renewal advanced by the proponents of CTW are critiqued. Drawing on interviews with elected leaders and staff from some of the Canadian sections of the CTW unions, one of the largest Canadian unions, the Ontario Federation of Labour and the Canadian Labour Congress, this thesis examines some of the implications of the split in the AFL-CIO on the Canadian labour movement. As trade unionists in Canada consider different approaches to union renewal, one option is to embrace an approach similar to the CTW approach: greater cooperation with employers and a more "efficient" business unionism. Another approach is union renewal with a socialist character; developing working-class capacities to construct socialist alternatives and renew the labour movement as an instrument of working-class struggle.

Les accidents mortels en milieux de travail dans le district judiciaire de Montréal de 1890 à 1930 : recension et analyse à partir des rapports d'enquête des coroners - Dionne, Jean-Claude (Université de Montréal, 2007)
L’objet de ce mémoire est la recension et l’analyse des accidents mortels survenus dans les milieux de travail du district judiciaire de Montréal durant la période de 1893 à 1930. À partir des témoignages contenus dans les rapports d’enquête des coroners, nous analyserons les opinions des travailleurs, des contremaîtres, des coroners et des inspecteurs afin de connaître leur point de vue sur les accidents et de vérifier dans quelle mesure ils partagent les valeurs libérales de cette époque. Pour constituer notre corpus d’information, nous avons dépouillé chacun des 1527 dossiers des rapports d’enquête des coroners effectuée entre le premier janvier 1893 et le 31 décembre 1930. Ils constituent notre principale source à partir de laquelle nous établirons l’ampleur des accidents mortels et également analyserons les témoignages recueillis par les coroners, Pour fin d’analyse, nous avons réparti ces données sous les quatre décennies couvertes par notre étude et élaboré des tableaux statistiques établissant la distribution annuelle et décennale de ces accidents de même que l’âge et le sexe des victimes. Nous avons également distribué ces accidents par secteurs d’activités économiques et par catégories d’accidents. Si les employeurs, les contremaîtres et les inspecteurs des manufactures adhèrent aux principes de l’idéologie libérale de l’époque en attribuant aux travailleurs la responsabilité première des accidents de travail, les coroners et les travailleurs considèrent, par contre, dans une forte proportion (72 %) que les causes de ces accidents sont associés à des défaillances des divers éléments des lieux de travail et aux processus de production. Ils sont donc plus enclins à attribuer la responsabilité aux employeurs.
https://doi.org/1866/17912

[e]motions, Moments, and Transnational Connections: The Lived Experiences of Two Labour Migrants in Canada's Seasonal Agricultural Workers' Program - Ferguson, Nelson (Concordia University, 2007)
Labour migrants have been routinely categorised within social scientific thought as either abstracted economic entities or as victims of global processes beyond their understanding. A striking majority of attempts to understand processes of migration, especially in regards to "unskilled" Mexican migrant workers, have been informed primarily by macro-level economic approaches, while the social and individual factors at play have been largely pushed to the side. As such, the social lives and individual diversities of these migrants have received meagre academic attention. In acknowledgment of this gap, this current thesis focuses on the lived experiences of Hector-Alberto and Durango, two individuals engaged in a cycle of migration as participants in Canada's managed migration program, the Seasonal Agricultural Workers' Program. Through an ethnographic description of the everyday experiences of Hector and Durango, three relevant themes are explored: their individual relations to their work, their family, and their co-workers. As such, the present work aims to explore the varied experiences of migration and frame labour migrants as significant social actors rather than abstracted units or victims of social forces. The author encourages an engagement in a broader investigation of the "migrant experience"; to look beyond the idea of transnational migration as simply physical movements across national boundaries, but rather as groupings of processes with profound and diverse meanings to those involved. Perhaps such a perspective would play a role in revealing the complex myriad of interacting processes which combine under the umbrella term of "migration".
Keywords: Social sciences

The Working Class After the Vanguard: Process and Plurality in the Theory and Practice of Working Class Organization - Green, Brian Stephen (University of British Columbia, 2007)
This thesis examines what the two sides of class– capital and working class –have meant in left parlance, what these meanings imply about class struggle, and how they were put into political practice through Communist Parties and trade unions. Ideas about class and strategies for class struggle continue to be central to the left, as the various ways these are conceptualized give rise to very different answers to some common and persistent questions: Who is legitimately a worker and when? Why, how and with what result are certain struggles delayed or subsumed within others? At what point does self-criticism cross over to counter-revolutionary dissent? And what might continuing schisms over these questions tell us about traditional left organizations? The thesis traces the development of 'the left' from its key conceptual subject, the working class, through its two most widely-adopted organizational strategies in order to examine the poverty of the left's analytical and political traditions, particularly as regards (1) the notion of socialism as an alternative management plan and (2) ideas about capital and working class that stressed the embodiments of power relations rather than those relations themselves, and which were lifted directly from capital's own definitions of productivity. Finally, the thesis argues that insights from long-neglected Marxisms, certain critical post-structuralisms and the political strategies of some emergent anti-capitalist networks together offer the opportunity to produce a more fluid, and more liberatory left, imbued with: (1) an understanding of class as a relationship that does not inhere to individuals or organizations, and (2) a notion of the working class as a permanent resistance that has nothing whatever to do with a particular ideology or strategy; with (3) an analysis which emphasizes situational relationships of power that are at once racialized, gendered, sexualized, and classed; and (4) a political approach which draws means and ends together in an emphasis on resistance as the troubling of order, and revolution as a process of refusal.

"The Both of Us Have Battled": The Practices and Politics of Female Partners in the Canadian Seasonal Agricultural Workers Program - Hanson, Christina (Simon Fraser University, 2007)
Through an analysis of qualitative, ethnographic data, I locate the narratives of nine Mexican women married to migrants within the context of capitalist globalization, state policies, and local gender ideologies. In doing so, advocate for a theoretical approach to migration which combines elements of structural theories of migration and network theoretical approaches. These women's narratives position them at the juncture of capitalism and other social relations, and show them to be active agents in migration. Not only is their labour critical to the maintenance of migration patterns and the capitalist relations into which migrants and non-migrants are incorporated, but women's labour is also imbued with social meanings.
Keywords: Canada – Mexico – Migration; Canadian Seasonal Agricultural Workers Program; Gender and migration; Mexico – Emigration and Immigration – Social Aspects – Case studies; Non-migrating women and globalization; Seasonal Agricultural Workers Program (Canada); Social aspects of migration; Temporary foreign worker programs; Women – Mexico – Social Conditions

Plus ça change? A Comparative Analysis of the Seasonal Agricultural Workers Program and the Pilot Foreign Worker Program for Farm Workers in Quebec - Lowe, Sophia J. (Ryerson University, 2007)
For the last 40 years, migrant farm workers from the Caribbean and Mexico have been recruited to work temporarily on Canadian farms under the Seasonal Agricultural Workers Program (SAWP). In 2002, the pilot Foreign Worker Program (FWP) for low skilled migrant workers was initiated in the province of Quebec and under this program began the recruitment of Guatemalan migrant farm workers. Since the program's start, the number of Guatemalan migrants has nearly tripled and there seems to be a decline in the number of workers hired under the SAWP in Quebec. This paper examines the FWP's development, set-up, consequences and operation alongside the SAWP and shows how the Canadian state is expanding the number and flexibility of temporary worker programs. This paper draws attention to the neo-liberal context of migrant farm labour in Canada, pointing to the ways in which Canada's federal policies governing seasonal agricultural migrants and the agricultural labour market are exploitative and racist.
Keywords: Foreign Worker Program; Migrant; Seasonal Agricultural Workers Program; easonal; foreign labour; racism; temporary

Fast Food Alienation: Service Work and Alienation in British Columbia, 1968-1998 - Milloy, Jeremy Strachan (Simon Fraser University, 2007)
Since World War II, service work has become the major employment sector in North America. One of the most recognizable forms it takes is in the fast food industry, a multi-billion dollar business with outlets all over the globe. Little has been written about the history of this work, central to the functioning of the global economy and a key part of the move from an industrial economy to a consumer one. This move has changed work by examining BC's White Spot chain, which unlike almost any other has been unionized for over three decades. Drawing on union records an d oral interviews, it analyzes fast food unionism, evaluates organizing in the sector, and draws out workplace dynamics and processes; arguing that labour practices in this sector have been crucial in making work more exploitative.

The Empire Within: Montreal, the Sixties, and the Forging of a Radical Imagination - Mills, Sean William (Queen's University, 2007)
This thesis explores the wide variety of ways in which radical intellectuals and activists in Montreal used and adapted Third World decolonization theory to build a broad movement of solidarity and anti-colonial resistance from 1963-1972. Beginning in the early 1960s, activists and intellectuals in Montreal began drawing upon the language of Third World decolonization to resituate their understandings of themselves, their society, and the world in which they inhabited. Through their engagement with Third World liberation theory – and the closely related language of Black Power – radical intellectuals in Montreal sought to give new meaning to the old conception of humanism, and they worked to drastically expand the geographical frame of reference in which Quebec politics were generally understood. After analyzing the shifting meaning of decolonization in the period leading up to the late 1960s, this thesis explores the ways in which various groups adopted, built upon, challenged, and shaped the conception of Quebec liberation. Montreal’s advocates of women’s liberation, the city’s Black activists, defenders of unilingualism, and labour radicals were all deeply shaped by the intellectual and urban climate of Montreal, and by ideas of Quebec decolonization. They developed their own individual narratives of liberation, yet linked by the flexible language of decolonization, these narratives all greatly overlapped, forming a vast movement which was larger than the sum of its parts. If the concept of decolonization was extremely powerful, however, it was also highly ambiguous and contradictory, and activists only slowly came to an understanding of the multi-layered nature of colonialism in Quebec. By the early 1970s, the idea of decolonization was slowly abandoned by those advocating radical social change in the city. This thesis makes three interrelated arguments. First, it argues that radicalism in Quebec in the 1960s cannot be understood outside of the larger international context in which it emerged. Second, it attempts to rethink the ways in which different groups and movements during the 1960s interacted and fed upon each other’s analyses and learned from each other. And, finally, by looking at the centrality of Third World decolonization to the development of dissent in Montreal, it hopes to add new perspectives to the growing field of international Sixties scholarship, by insisting that history of the ‘West’ was profoundly shaped by its interactions with the Third World.

Women's Experiences and Representations of Diversity Management and Organizational Restructuring in a Multinational Forest Company - Mills, Suzanne Elizabeth (University of Saskatchewan, 2007)
This thesis examines the relationship between worker identity and workplace practices from the perspectives of white and Aboriginal women working in a multinational forest company in the northern prairies. Over the course of three manuscripts I demonstrate the salience of ascribed and constructed identities of women to their experiences and representations of forest employment and corporate discourse. Setting the context for the remainder of the thesis, the first manuscript presents an analysis of employment segregation by gender and Aboriginal identity in Canada’s forest sector in 2001 using segregation indices. Results demonstrate that forest employment was vertically segregated by both gender and Aboriginal ancestry in the forest sector in 2001. Men and women of First Nations ancestry were over represented in less-stable and lower paying occupations in woods based forest industries, and both white and First Nations women were over represented in forest services and clerical occupations. To explore women’s perceptions of company practices of diversity management and restructuring, I then analysed interviews with women working in forest processing using critical discourse analysis. In my second manuscript, I demonstrated how women’s representations of diversity management practices were linked to their social identities in terms of Aboriginal identity and class. Yet, as a whole, these representations prompted a questioning of the meaning of difference within diversity management, and of diversity management’s ability to further the interests of marginalised workers. My third manuscript examining representations of restructuring, argues that there is a two way relationship between women’s identities as workers and their representations of restructuring. Whether women reproduced or resisted restructuring was linked to their presented work identities and restructuring and practices in turn were helping to shape women’s worker subjectivities. Results from this thesis demonstrated that how women represent themselves and workplace practices is related to their different experiences in the specific set of social relations of forestry work in the northern prairies.

Constituting Authority: Policing Workers and the Consolidation of Police Power in Vancouver, 1918-1939 - Russwurm, Lani (Simon Fraser University, 2007)
Policing in Vancouver was transformed by the labour unrest of the interwar period, culminating in a campaign carried out by a new civic regime that assumed power in response to a general strike threat. Complicating the process was that police workers were considered unreliable for policing labour disputes, especially since they unionized under the threat of a general strike in 1918. The challenge of “constituting authority” was therefore to render the police a reliable instrument against working class unrest. This study traces the development of policing through the postwar spate of waterfront strikes to the 1930s anticommunist campaign that carried the struggle into the political arena. Even as police power was being consolidated in the municipal police institution, rank and file police were undermined by tactics long used against other workers, namely labour spies and police specials. Like other workers, police resisted, modifying the process of change as a result.

The Stelco Saga: Restructuring and Resistance in the Neo-Liberal Era - Stone, Brendan (McMaster University, 2007)
Global market conditions have led to large corporate bankruptcies in recent years, particularly in the steel sector. Bankruptcy restructuring under the u.s. Chapter 11 or Canadian Companies' Creditors Arrangement Act [CCAA] places employee pensions at risk. In response to concessionary restructuring, the U.s. arm of the United Steelworkers [USW] intervened in several steel sector bankruptcies, developing restructuring solutions that led to partial or near-complete restoration of pensions and collective agreements. In Canada, during Stelco's troubled bankruptcy process between 2004 and 2006, Steelworker locals employed this interventionist method to prevent pension and collective agreement concessions. Scholars, such as Frost and Bacon, implicitly provide a rationale for union intervention into bankruptcy restructuring. They argue that union intervention in general corporate restructuring allows workers a greater voice in the process, leads to optimal results, and prevents union irrelevance. Frost outlines several criteria for maximizing union success during restructuring: the strength of union intra-organizational and external ties; the responsiveness of the union leadership towards the interests of the membership; and the ability of the union to access information and participate at all levels of the process. Many of Frost's recommendations were critical to the success of the USW locals at Stelco in achieving their bargaining and restructuring goals. Unlike in the more cooperative restructuring examples studied by Frost and Bacon, however, Stelco's Canadian locals employed a very assertive stance, since management exhibited initial hostility to union intervention. The union also found it necessary to enlist the help of government. While union intervention in bankruptcies remains a controversial process, it is one possible solution for troubled manufacturing unions, represents an overall USW push towards greater involvement in management, and may even lead towards an exit for labour from the discarded "post-war compromise."

Mouvements sociaux, syndicats et action politique à Montréal : l'histoire du FRAP (1970-1974) - Comby, Marc (Université de Montréal, 2006)
Ce mémoire relate l’expérience du Front d’action politique des salariés à Montréal (FRAP) de 1970 à 1974, un parti municipal émanant directement des milieux syndicaux et populaires. Après avoir présenté les grands traits de la conjoncture sociale, économique et politique de la décennie 1960 au Québec, nous analysons les conditions objectives qui ont favorisé l’émergence du FRAP à Montréal (problèmes sociaux, administration municipale autoritaire, logements insalubres, etc.). Le FRAP est fondé en mai 1970 et présente des candidats contre le maire Jean Drapeau aux élections du 25 octobre suivant. La Crise d’octobre et l’imposition de la Loi des mesures de guerre déroutent le FRAP qui ne fait élire aucun candidat. Les mois et années qui suivent, les groupes sociaux s’éloignent du FRÀP et ce dernier a vainement espéré que les organisations syndicales de la région de Montréal concrétisent l’idée qui avait été à l’origine de sa création, à savoir un parti politique propre aux travailleurs et aux travailleuses. Le FRAP met fin à ses activités au début de l’année 1974 quelques mois avant la naissance d’un nouveau parti municipal, le Rassemblement des citoyens de Montréal (RCM).
https://doi.org/1866/16834

A Detailed Profile of Union - Non-Union Wage Inequality in Canada: 1997-2004 - Easton, Mark David (University of Waterloo, 2006)
This thesis is focused on examining the extent of union-nonunion wage inequality in Canada from 1997 to 2004, using data from the Canada Labour Force Survey collected by Statistics Canada. The research is either directly or indirectly guided by two main measures of union-nonunion wage inequality. The first measure is the wage differential , which examines the difference between the union and nonunion wage after controlling for other relevant factors in a regression model; and the second measure is an account of wage dispersion or wage spread, which effectively explains how internally equitable the union-nonunion wage distribution is in relation to the average wage, after controlling for other relevant factors in a regression model. Each chapter tackles a different hypothesis or subject relating to Canadian union-nonunion wage inequality as investigated from the Canada Labour Force Survey Dataset, and is guided by an effort to explore issues or patterns not previously addressed in the extant literature. The initial analyses found that the union-nonunion wage differential across Canada was normally eleven to sixteen percent from 1997 to 2004. The research also examined three advanced topics in Canadian union-nonunion wage inequality. Analyses of the industry, occupational, and demographic trends in Canada over the past eight years showed that there is some evidence to suggest that demographic changes in union density does affect union-nonunion wage inequality, but this relationship is not conclusive. This research also addressed the unusual finding of higher hourly wages among parttime females. This difference was not present after conducting a more rigorous regression analysis within both sectors. However, it was found that the marginal male wage premium could largely be explained by the combined effects of establishment size among males in the union sector, as well as educational attainment among males in the union sector. Further investigation of some unexpected interaction effects of union status and establishment size and union status and job tenure in relation to the wage, revealed that these combined effects still generated comparative over the nonunion group, but only up to a certain level of tenure or establishment size. Finally, an analysis of whether union density has mattered at all in Canada for promoting higher wages, reveals that the general effects of union density on the wage are relevant only within a certain wage range and within certain industries.
Keywords: Social sciences

Protection of Migrant Agricultural Workers' Rights - Gutierrez, Gonzalez Israel (McMaster University, 2006)
This thesis investigates several issues related to the provisions afforded by aspects of the Canadian welfare state to protect the rights of migrant labour participating in the Canadian Seasonal Agricultural Workers Program. In the introduction and literature review, I provide the background of the program and present the nature of the issues that surround it. I also outline the problems that migrant agricultural workers face while participating in the program. These are mainly due to the few provisions that are extended to this secondary sector labour group, a group of workers that is barely visible to Canadian society. In the main part of the thesis, I analyze the two instruments that allow the entry of these workers into Canada and the different pieces of Canadian legislation that are relevant to protecting legitimate rights of any person who works in this country. More importantly, I also present findings derived from interviews with migrant agricultural workers and key informants from advocacy groups and the labour movement regarding those provisions. Based on their in Sights and on the dual market theory, I scrutinize the position of the Canadian welfare state concerning the legitimate provisions migrant workers should be entitled to and how the globalization context influences that position. I conclude with a series of ideas that, in my opinion, could positively affect this labour group's welfare status.

Globalization and the Mexican-Canadian Seasonal Agricultural Worker Program: Power, Racialization and Transnationalism in Temporary Migration - Hennebry, Jenna L. (University of Western Ontario, 2006)
This research investigates the formation and maintenance of power relations within the organization and everyday practices of work and transnational living, and the social and economic impacts among Mexican migrants and their families participating in the Seasonal Agricultural Worker Program (SAWP). Through the analysis of the qualitative data collected through ethnographic case studies in Mexico, 350 hours of participant observation, and semi-structured interviews with 25 migrant workers, 5 farmers and 5 representatives from other state and non-state intermediaries, findings have emerged pertaining to three research themes: power, racialization and transnationalism. This research finds that Mexican migrant workers are consistently located in subordinate power positions in the organization and the everyday practices of the SAWP; and governments, employers, and other intermediaries have significant control over migrants' daily lives and their migration parameters. Racialization processes in both the institutional and everyday practices of the SAWP produce, maintain, and legitimize a system of temporary migration characterized by imbalanced power relations and the unequal allocation of resources and rights through the differentiation of the "Mexican migrant worker" with reference to race and ethnicity. Migrant workers and their families actively participate in transnational practices that are integral to seasonal migration, including the family networks that facilitate entry into the program, the "migration work" performed by women, and the use of information and communication technologies (ICTs). This essential "migration work" involves preparing the family for migration and sustaining the transnational family through managing and/or working within family farms and small businesses, receiving and managing international remittance transfers and telephone calling, managing and utilizing remittances for daily living and development, and performing carework. These findings support the "transnationalization of culture" hypothesis, and indicate that a gendered culture of migration is emerging within the SAWP. It is argued that the SAWP is an exemplar of "time-space compression" in action which leads to the exploitation and subordination of "Mexican migrant workers." Temporary migration systems like the SAWP are seen as recursively related to globalization, where foreign labour dependence and remittance economies are created and perpetuated through globalization and a "migration industry" powered by new information and communication technologies.
Keywords: Globalization; Mexican-Canadian Seasonal Agricultural Worker Program; Racialization; Seasonal agricultural workers; Social sciences; Temporary migration; Transnationalism

Le Conseil central des syndicats nationaux de Montréal (CSN) à l'heure de la radicalisation syndicale : 1968-1980 - Poirier, Stéphanie (Université de Montréal, 2006)
Ce mémoire porte sur le syndicalisme québécois dans les années 1960 et 1970 alors qu’il traverse une phase de bouleversement et qu’il radicalise son idéologie. Nous nous penchons plus particulièrement sur le cas de la CSN qui affermit sa critique du capitalisme avec la publication de textes d’orientation socialiste tels que Il n'y a plus d’avenir pour le Québec dans le système actuel et Ne comptons que sur nos propres moyens. Parmi les instances de la centrale, il y a les conseils centraux régionaux dont celui de Montréal, le plus imposant en terme d’effectifs (près de 60 000 en 1968). Rassemblant la frange la plus militante de la centrale, il a pour rôle l’éducation et l’action politique des membres. Le Conseil central des syndicats nationaux de Montréal (CCSNM) se trouve au centre de la tourmente sociale et nationale au cours de ces deux décennies alors qu’il est dirigé par la figure imposante et colorée de Michel Chartrand, président de 1968 à 1978. Dans l’historiographie, le Conseil central de Montréal est souvent considéré comme un haut lieu de la radicalisation syndicale. En analysant son discours et ses actions, nous démontrons qu’il prend effectivement des positions radicales et qu’il défend des opinions nationalistes. Malgré le fait qu’il tente de passer à l’action politique et milite pour la création d’un parti de travailleurs, le Conseil se caractérise principalement par son discours contestataire et sa critique acerbe du capitalisme. Nous verrons qu’il développe une position nationaliste indépendante au cours de la période, en se dissociant du projet du Parti québécois, qu’il juge bourgeois. Bien que les relations entre la CSN et le Conseil soient tendues, ce dernier a tout de même un impact important sur la CSN, particulièrement au niveau de la protection de la langue française et sur la position adoptée par la centrale au référendum de 1980. Le Conseil constitue donc un acteur important de la radicalisation de la société québécoise des années 1960 et 1970 en influençant la CSN, le mouvement syndical ainsi que les milieux de gauche à Montréal.
https://doi.org/1866/16824

L'image des syndicats dans les éditoriaux de trois quotidiens montréalais lors de la première année du gouvernement québécois dirigé par Jean Charest (avril 2003 - avril 2004) - Posca, Jean-Simon (Université du Québec à Montréal, 2006)
Ce travail décrit et fait l'analyse de l'image des syndicats dans les éditoriaux des quotidiens payants montréalais lors de la première année au pouvoir du gouvernement québécois dirigé par Jean Charest (avril 2003 à avril 2004). Il se concentre sur les éditoriaux traitant des luttes entre les syndicats et le gouvernement Charest. Il examine les éditoriaux relatifs au syndicalisme parus dans Le Devoir, La Presse et The Gazette. Le travail présente et explique les ressemblances et les divergences apparaissant entre les différents journaux dans l'image que ceux-ci renvoient des syndicats.

"A Very Conservative Radical": Reverend Robert Connell's Encounter with Marxism in the BC CCF - Price, Christine (Simon Fraser University, 2006)
The historiography of the British Columbia Cooperative Federation differs from that of other provincial CCF groups for its lack of attention to the participation of religious reformers in shaping the party's early history. Yet the first CCF House Leader in the province, Reverend Robert Connell, was a fervent believer in the social gospel and in the goals of ecumenism. His attempts to bring "Christian principles" into politics resulted in a battle between reformers and radicals in the party, ultimately resulting in his departure from political life. The division of the BC CCF in 1936 as a result of what has become known as the "Connell Affair" created a loss of momentum for the party which lost its status as Official Opposition in the 1937 provincial election. This event presents a unique opportunity to study the interaction of a social gospel inspired Christian reformer with firmly irreligious supporters of Marxism.

Organized Labour and the Constitutional Question - Savage, Larry (York University, 2006)
This dissertation examines Canada's constitutional question through the lens of the labour movements in both English Canada and Quebec. The existence of two distinct labour movements in Canada has meant that political struggles that have typified national politics are also in evidence in labour politics. The sovereignty-association partnership agreement between the Canadian Labour Congress and the Quebec Federation of Labour provides a good example of the pervasiveness of this dynamic and discourse. The dissertation examines this relationship specifically, and the constitutional politics of labour organizations in English Canada and Quebec, more generally, with a view to explaining how Canada's constitutional questions have been reflected in the politics of organized labour.
Keywords: Constitutional question; Social sciences; Sovereignty-association partnership agreement; organized labor

Masters and Servants: The Hudson's Bay Company and Its Personnel, 1668-1782 - Stephen, Scott P. (University of Manitoba, 2006)
During its long first century (1670-1782), the Hudson’s Bay Company (HBC) developed personnel practices not on the basis of abstract policy but by patching together experiments and expedients. Its initial vulnerability increased the value of loyal and experienced servants, and frequent shortfalls in wartime recruitment allowed old hands to demand and receive higher wages and gratuities. Peace after the Treaty of Utrecht in 1713 allowed the Company to prune its payroll and to resume the carefully optimistic expansion that French attacks had interrupted in 1686. This required a larger labour force, but recruitment processes remained relatively unchanged from previous years (although Orkneymen became increasingly prominent). Expanding operations in the mid-eighteenth century imposed greater regularity on existing ad hoc methods of recruiting and retaining personnel, but labour needs did not expand rapidly enough to unduly strain those methods. Increasing inland travel and trade after 1743 placed new demands on servants by requiring that ‘extraordinary’ labour become ‘ordinary’. The Committee discovered that this could only be done with ‘encouragement’, the slow pace of which hampered inland ventures into the 1780s. Inland operations changed the nature of HBC service and influenced the way master, factor, and servant interacted; they also illuminated the practices and assumptions which had been prevalent since Utrecht and probably before. The HBC drew its labour force from the competitive labour ‘market’ of early modern Britain: the movement of men to and from the Bay was an aspect of domestic labour mobility. The relationship between the Committee and their employees was that of master and servants, heavily influenced by the circumstances of trading in Hudson Bay. Labour relations within HBC posts were framed by the dominant social construct of early modern Britain, the patriarchal household-family, made up of a master (the patriarch) and a family of kin, apprentices, and servants. Men at all levels of the Company hierarchy could try to shape the reality of their HBC experiences, but did so in terms of commonly accepted ideals. Deferential behaviours and strong vertical ties existed alongside tension and negotiation: the Committee and their servants all understood the nature of ideal master-servant relationships, but they also had experience of the realities of life in various kinds of households. The Company’s servants internalized and practised the expected values of deference and submission, but did so without abandoning or deferring their own self-interest; indeed, they could use their mastery of the language to advance their own interests. The household-factory was the fundamental social unit of HBC establishments. Although membership changed, the institution maintained continuity over time. Furthermore, each household-factory was internally held together, and bound to other household-factories and to the London Committee by ties of patronage, brokerage, and friendship, that mediated the network of horizontal and vertical relationships.

Faith and Factory: Russian Mennonite Workers in Twentieth-Century Manitoba - Thiessen, Janis Lee (University of New Brunswick, 2006)
[This thesis is] a labour history of Russian Mennonites employed in three Mennonite-owned factories in Manitoba: Friesens Corporation of Altona, Loewen Windows of Steinbach, and Palliser Furniture of Winnipeg. Each of these businesses had a primarily Mennonite workforce at their founding, and eventually became the largest employers in the community in which they were established. This comparative microhistory makes a significant contribution to the literature: though approximately one-quarter of North American Mennonites are working-class, few scholarly works have investigated their experiences. The history of immigration of these Mennonites is important in understanding their adaptation to North American capitalism. Immigrants had common experiences of some aspects of settlement, such as language acquisition and finding employment. Immigrants exhibited a variety of responses to government efforts to promote assimilation, and demonstrated different attitudes toward job security and expectations for their children, in part because of their diverse prior experiences of war, religious conservatism, and prejudice in their country of origin. The result was the development of an increasingly urban and heterogeneous Mennonite community in Manitoba, which perhaps contributed to the failure to develop a strong sense of class consciousness among them. The historical development of Mennonite religious thought in the twentieth century is connected to the geographical shift of North American Mennonites from rural to urban environs. This move necessitated a re-assessment of Mennonite religious beliefs, particularly of their understandings of 'Gelassenheit ', to nonresistance, and 'agape' love. The Christian's responsibility to the world came to be stressed at the expense of traditional values such as submission to the community and separation from the world. Religious belief had a role in restraining the behaviour of both workers and owners, encouraging the former to accept work discipline, and limiting the latter in their conspicuous consumption. In a case study, Barthes' semiological approach is used to demythologize an advertising campaign at Loewen Windows as a means of examining the linkages between religion and capitalism. The role of religion differentiated the operation of paternalism at these businesses from their non-Mennonite counterparts. Though Mennonite workers rarely expressed their views in class-conscious ' language', the 'content' of their remarks, particularly with respect to the labour process and their autonomy, points to the existence of a class division in these factories. The nature of their employment as factory workers affected not only their job mobility and security, the speed of their work, their sleeping patterns and social lives, but also their identity. Class differences between Mennonite employers and employees clearly existed; class consciousness on the part of workers is less evident. With the transformation of Friesens Corporation, Loewen Windows, and Palliser Furniture from small family businesses to large corporations, the relationship between Mennonite workers and their employers was reinterpreted. Employers made use of Mennonite religious motifs to craft a common ethos, but increased ethnic diversity in the workforce at Palliser Furniture, together with objective class differences between workers and owners at all three companies, resulted in some splits in the unity of the Mennonite workplace. The interplay of competing interests nonetheless resulted in redefinitions of ownership rights and their meaning for workers with respect to profit sharing and employee share ownership, as well as several unsuccessful attempts to unionize. The tension between Burkholder's emphasis on social responsibility, as exhibited by labour's demands for economic justice, and Hershberger's insistence on avoidance of confrontation was evident in the struggle of Manitoba Mennonites with their response to labour activism in the 1970s. Pacifism often had been dismissed as passivity in the past; now the adherence to the principle of nonviolence could be seen as an excuse for accepting economic exploitation. Mennonite support for cooperatives and credit unions could have translated into support for labour unions, but in late twentieth-century Manitoba, it did not. Though North American Mennonites' attitudes toward unions may have undergone change during this period, they continued to avoid becoming members. The conclusion explores whether Mennonite involvement in industrial capitalism is (or can ever be) in any way distinct from that of secular participants. Are there theological resources within Mennonitism that can mount an effective challenge to the negative results of global capitalism? This work is a modest attempt to contribute to the debate, both within the Mennonite community and without, regarding the possibilities for social and economic transformation. It is also an attempt to argue for the relevance of the consideration of religion in scholarly discourse in general, and historical study in particular.
https://archives.mhsc.ca/index.php/52ky-4qm6-qwb4
Keywords: Employment; Family-owned business enterprises; History; Labor; Manitoba; Mennonites; Religous aspects

Direct Action, Subsidiarity and the Counterhegemonic: Three Case Studies of Antipoverty Activism in Twentieth Century Canada - Thompson, David Alexander (University of Victoria, 2006)
An analysis of three poor people's movements in twentieth century Canada serves to wrest the ideas and activist tradition of Canada's poor people from historical obscurity. Between 1932 and 1935, the Communist-inspired Vancouver unemployed councils engaged in direct actions to challenge Depression-era social policy, capital and the police. The arrival of the modern post-war welfare state did not end poverty; however. Vancouver antipoverty activists were circumscribed by society's relative affluence and organizational and sectarian debates within labour councils and the antipoverty movement. Finally, since 1989 the Toronto-based Ontario Coalition Against Poverty (OCAP) has extended antipoverty activism to include the issues of immigrants, First Nations, women and children. Drawing on theorist Antonio Gramsci and the socialist-anarchist tradition, this thesis posits that direct action and a subsidiarity relationship between activists and their community are essential to the success and longevity of poor people's movements.

"Still Raining, Market Still Rotten": Homeless Men and the Early Years of the Great Depression in Vancouver - McCallum, Todd (Queen's University, 2005)
Single transient homeless men are one of the archetypal figures of the chaotic decade known as the Great Depression. They are also a misunderstood group, commonly associated with a degraded and hopeless existence. This thesis focuses on homeless men, both on the road and in Vancouver, in the period from the fall of 1929, with the collapse of North American stock markets, until the spring of 1932, with the breakdown of the provincial government's relief camp scheme. It argues that those involved in the relationships of charity provision, whether homeless recipient or government bureaucrat, characterized the world of relief with the same terms they used to understand the normalized world of the capitalist economy. Homeless transients flocked to Vancouver by the thousands. Many became the rank-and-file backbone of Communist-led protest movements. Consistently, these movements demanded relief at union rates, challenged the gendered, racial and national categories that divided the unemployed, and rejected outright the oppressive relief measures accorded transients. In response, the municipal government sought to introduce Fordist methods of business management, rationalizing the processes of relief provision with an eye to efficient administration and surveillance. Relief was not a one-sided transaction-a gift from one party to another-but an exchange. When offering the poor food, shelter, fuel and clothing, public and private charities became involved in commercial relationships with the city's service industries. Businesses across Vancouver clamoured to get their share of relief money, hoping to translate some of the money spent on the unemployed into profit. With state-run relief camps, governments created one of the sharpest contradictions of the 1930s, unemployed workers who worked for a living, but for substandard rates of relief. Officials seized upon the crisis to initiate a program designed to develop British Columbia's economic infrastructure. The work of the jobless would thus pay dividends by enabling an increased rate of economic growth once the crisis had passed. In these ways, relief became an industry. The hundreds of people who wrote about tramps during the 1930s twinned the objectification and the commodification of transiency. Whether espousing a humanitarian or a hateful view of hoboes, these authors almost unanimously agreed that the tramping life had to be destroyed. Hoboes would vanish from the Canadian landscape because their lives were without value. For their part, the hoboes who put words on paper ranged across a host of subjects pertaining to life on the road and life in the city. While some cried out against what they saw as the oppressions of transient life and envisioned a future in which they would be reintegrated into society, others lauded the camaraderie and mutuality amongst tramps. For this group, the hobo life was an end in itself, valued because it enabled them to live free from the exploitation that was the lot of wage workers.
OCLC: 59135675
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Industry, Ideology, and Social Formation in British Columbia, 1849-1885 - Morton, Jamie (University of Victoria, 2005)
This study examines how the systems of production of the commodity exporting industries of pre-1885 British Columbia contributed to the social formation of the region. Such industries provided the economic base for post-contact development and non-Native settlement of the region, mediated by the cultural values of immigrant and indigenous populations. The intent here is to synthesize a more inclusive model to clarify how these economic and cultural factors intersected to produce a distinct regional society. Beginning with Ian McKay’s suggestion to interpret the history of Canada as a process of naturalizing the liberal order, this study moves the analysis away from microstudies of individual industries or social groups in order to emphasize the way in which a broader vision became naturalized. This approach avoids some of the simple dichotomies of class and race that have informed much of the historiography of BC, in favour of a more nuanced analysis that emphasizes the negotiated process that leads to social consensus. Beginning with the merchant capitalist relations of the fur trade, and accelerating with the 1858 gold rush, BC became understood as a place that provided opportunities for economic and social mobility through participation in commodity exporting ventures. A consensus emerged that emphasized the producer ethic [the economic and cultural value of independent producers], and the creation of a meritocratic socio-political environment to support opportunities for achieved, rather than ascribed, social position. This attracted Euro-North American immigrants hoping to escape social restrictions or proletarianization by achieving independent producer status. Such a goal meant that these immigrants resisted waged labour, creating a chronic shortage that impeded industrial development. This was filled with Chinese immigrants or Aboriginal participants, attracted by the prospect of converting earnings into increased status in their originating societies. Combining the demand for labour with racial ideology, certain jobs were racialized, and BC industries were typified by split labour markets, with an upper echelon comprised of occupationally-mobile Euro-North American workers, and a lower echelon defined by race as well as skill, with little opportunity for mobility. In turn, this contributed to naturalizing ideology concerning race, class, and social position. The emphasis on the producer ethic contributed to an artificial division between “producers” and “agents,” with the former celebrated, while the latter, arguably more important to the systems of production by providing links to export markets, are portrayed less favourably. A commodity exporting, producer-centric variant of the liberal order was naturalized in nineteenth century BC, providing the logic for social and political development, and explaining how certain groups were valued, and either integrated into or excluded from hegemonic society. The degree to which individuals or groups conformed to the naturalized values of the emerging society largely determined their social position in the nineteenth century, and their subsequent treatment in the historiography.

From Conquest to Capitalism: The State, Class, and Capital in British North America, 1760-1860 - Peters, John (York University, 2005)
This thesis traces the transformations in state, class, and politics in British North America from 1760-1860, and how these facilitated the emergence of wider economic change. Building on recent studies in political economy, Marxist and economic history, as well as historical sociology, it employs a class power model of historical change to explain how and why colonial Canada's political economy developed. The argument also draws upon comparative political economy to highlight how different class structures and different forms of political institutionalization shaped political economic regimes and long-run forms of economic growth. The case study analysis of British North America within a wider comparative context demonstrates that class interests, institutions, and policy making were critical to state building and changes in state-society relations, above all to state 'autonomy' and class 'embeddedness'. Agrarians and commercial classes struggled over economic benefits and the reins of political power. But how these classes forged coalitions and how their conflicts were institutionalized within the state determined whether or not new productive dynamics emerged. By the mid-19th century, with greater autonomy, colonial governments across the North American colonies designed institutions, laws, and policies to improve taxation, build infrastructures, enhance the rule of law, and extend the contractual equalities necessary to commercialize the economy. With greater class embeddedness, broader class coalitions of agrarians and merchants actively reshaped agrarian property and agricultural labour to conform to the structures of a market economy, and enacted new market law to allow for the expansion of free labour markets, trade, commerce, and small manufacturing. Looked at comparatively, the thesis claims, 19th century colonial British North America emerged as a 'Liberal Settler' society, led by a diverse coalition of agrarians and merchants. Despite its many state and class particularities, this crystallization of settlers, merchants, and Imperial market-directed politics made colonial Canada a variant of Britain's own liberal political economy, and very similar to other growing settler countries such as the United States. Exploring the connections between state, class, and politics, the thesis concludes, can tell us much about why and how these distinct historical patterns emerged, and why 19th century political economies changed in ways that fostered the development of capitalism.
Keywords: Capital; Capitalism; Conquest; Political economy

The Making of CUPE: Structure, Democracy and Class Formation - Ross, Stephanie (York University, 2005)
This thesis explores the nature and challenges of democracy within unions through an historical examination of the emergence and early years of the Canadian Union of Public Employees (CUPE). Formed by a merger of two pre-existing unions in 1963, CUPE casts new light on the Marxist, Michelsian and Institutionalist theoretical approaches to union democracy. The thesis calls into question the narrow and ahistorical link made between centralization, oligarchy and effectiveness on the one hand, and decentralization, democracy and ineffectiveness on the other. Instead, the case of CUPE shows that unions are subject to contradictory pressures and that neither centralization nor decentralization is inherently more democratic. Union democracy is part of an historical process of class formation, in which both union purposes and the boundaries of the democratic community (which can make legitimate claims on members' solidarity and self-discipline) are struggled over. As such, it is possible that decentralizing forces can place narrow and sectionalist priorities over the interests of the broader community. Moreover, the thesis argues that the use of merger as a method of forging greater class unity is itself problematic. The merger which created CUPE involved a protracted struggle over which model of union would prevail. The compromise which was reached entrenched a self-reinforcing cycle of autonomy-seeking by union locals which, over the long term, prevented the development of an effective national union capable of carrying out the democratic will of the membership as a whole. As such, through an historical excavation of the roots of contemporary crises in CUPE, the thesis points to the important way in which the outcomes of past decisions come to structure future political possibilities for unions and other social justice organizations.
Keywords: Canadian Union of Public Employees; Class formation; Democracy; Labor Unions; Social sciences

Oshawa Autoworkers: Social Integration and Oppositional Class Consciousness Among the Unionized Workers of General Motors - Roth, Reuben N. (University of Toronto, Ontario Institute for Studies in Education, 2005)
Many social theorists (Goldthorpe, Lipset, Giddens, Hout, Brooks and Manza) have portrayed members of the Western industrial working-class as accommodative and resistant to a class-based social revolution. They suggest that an affluent proletariat has seen its oppositional class-consciousness subverted and transformed by the 'cash nexus' into various forms of social integration. With reference to Mann's (1973) measures of class-consciousness typologies and Livingstone and Mangan's (1996) study of Hamilton steelworkers, I explore expressions of working-class consciousness among organized workers at one of Canada's largest industrial union locals, the Canadian Auto Workers (CAW) Local 222 at General Motors, in Oshawa, Canada. I accomplish this via an examination of the existence and degree of working-class imagery, class identity, and oppositional working-class consciousness among this group of workers on the basis of measured responses to a survey questionnaire (N=102), in-depth interviews, and participant observation. My thesis asserts that Oshawa autoworkers' material advantage is insufficient to transform their proletarian consciousness. I have found that among Oshawa autoworkers there is a shared view of Canadian society as class-based, a clear working-class self-identification and measurable forms of oppositional working-class consciousness.
Keywords: Autoworkers; General Motors; Ontario; Oppositional class consciousness; Oshawa; Social integration; Social sciences; Unionized

Engaging Women’s History Through Textiles: Enhancing Curricula with Narratives of Historical Memory - Wheeler, Eileen Margaret (University of British Columbia, 2005)
During the late nineteenth and early twentieth centuries, racism, in the form of white supremacy, shaped relations between whites and Chinese British Columbians. In resisting and accommodating to white supremacy, the Chinese were active participants, along with the members of the dominant society, in shaping these relations. White supremacy was consequently a dynamic system, one whose many parts were continually in flux, and whose central constructs—notions of "race" and British Columbia as "a White Man's province"—were largely political in nature. The thesis argues that white supremacy, as both ideology and organization, was deeply imbedded in British Columbia society. Exclusion based on "race" was incorporated into government institutions as they were remade at Confederation in an effort to enhance the power of white male property-owners. By the early twentieth century, ideological constructs of "the Chinaman" and "the Oriental" were used as foils in the creation of identities as "whites" and as "Canadians." The official public school curriculum transmitted these notions, while schools themselves organized supremacy in practice by imposing racial segregation on many Chinese students. In reaction, the Chinese created their own institutions and ideologies. While these institutions often had continuities with the culture of South China, the place of origin of most B.C. Chinese, they were primarily adaptations to the conditions of British Columbia, including the realities of racism. Chinese language schools played an especially important role in helping to create a Chinese merchant public separate from the dominant society. This public was at once the consequence of exclusion and the greatest community resource in resisting white supremacy. The study concludes by questioning the workability of contemporary anti-racist strategies which treat racism as a marginal phenomenon, or as merely a set of mistaken ideas. Instead, it suggests that such strategies must recognize that racism is one of the major structures of Canadian society.

The Communist Party of Canada during the Great Depression: Organizing and Class Consciousness - Burger, Anne (Simon Fraser University, 2004)
Canada experienced its worst economic crisis during the Great Depression of the 1930s with unprecedented numbers of Canadians suffering extreme economic and social hardship. Survival and struggle to change those conditions became as much a mark of the times as the economic circumstances themselves. The Communist Party of Canada (CPC) was one organization that played a significant role in this national upsurge of struggle. The Party believed that the worsening material conditions would engender class consciousness of Canadian workers, leading to the overthrow of the capitalist system to achieve a worker-farmer socialist state. The Party was instrumental in organizing workers, farmers, the unorganized and the unemployed, however, it was not successful in raising Canadian working class consciousness to a revolutionary level. The factors that will be analyzed as being the main contributing factors to the Party's limitations are the CPC1srelationship with the Comintern, repression by the Canadian state, and dominant ideology that prevailed in Canada during the Depression. From its inception in 1921 the CPC worked assiduously to meet the needs of Canadian workers in a rapidly changing economy in the 1920s and one that was also collapsing in the Depression. In many ways it recognized Canadian workers' needs in these times and was at the head of the labour movement fighting for workers' needs and defending them. However, the CPC was somewhat hamstrung by its very close relationship with the Comintern allowing this international communist body to dictate almost every move it made whether or not it was the best for Canadian workers. State repression of the CPC and labour movement, also had a curbing effect on the advancement of the CPC in its work with Canadian workers, forcing the Party underground, decimating its leadership and intimidating Party activists, unions and workers. Finally, dominant ideology during the Depression, in spite of serious threats by alternate sets of ideas, particularly those promulgated by the CPC, largely stood its ground as defender of the present capitalist system that relied on the exploitation of Canadian workers for its survival.

Acting in the Name of Culture? The Participation of Organized Labour in the Canadian Broadcasting Policy Process - Coles, Amanda (Toronto Metropolitan University, 2004)
The thesis examines the role, efficacy and influence of the five national English-language independent film and television production sector unions in the Canadian broadcasting policy network. While labour is typically classified as a civil society organization within policy networks studies, this thesis will examine the blanket applicability of this typology in analysing labour's engagement with issues that involve both their vested economic/industrial interests as well as broader social/cultural goals, using the unions' engagement with the issue of Canadian dramatic programming from 1998 to present as a case study.

Reconsidering Staple Insights: Canadian Forestry and Mining Towns - Dignard, Louise (Carleton University, 2004)
The purpose of the thesis is essentially to elaborate, and to a lesser extent to test the relevance of a theoretical framework focussing simultaneously on the spheres of industry, work and community in staple-specific contexts, explicitly in Canadian forestry and mining single-industry towns (SITS). The framework builds two ideal types of these towns by drawing from the main approaches that have addressed the topic in political economy, labour and community studies. The core underlying argument is that a reconsideration of some neglected staple insights constitutes a legitimate endeavour. The framework stresses that forestry SITs have more: of an elite model of power structure, separate work and community social arrangements, individualistic income strategies, as well as lower class consciousness and numerous contradictory class locations; while mining SITs have more: of a class model of power structure, overlapping work and community arrangements, income strategies framed in secondary relations terms, as well as a higher class consciousness and fewer contradictory class locations. After a brief introductory chapter, the second, third and fourth ones extensively review and interpret the literature, gathering empirical material and theoretical considerations useful to the comparative theoretical framework. The latter is detailed and its claim circumscribed in Chapter five; its relevance is tested in the two last chapters by using it as a backdrop to explain staple specific patternings regarding the organization of work in the main resource sector and women's experience in the family.
Keywords: Forestry and mining towns; Single-industry towns; Social sciences; Staple insights

Exploring Decentralisation in Canada: Devolution of Labour Market Policy - Gray, Erin (University of Wales, Swansea, 2004)
This thesis entails the study of both why and how decentralisation of government authority takes place. Decentralisation in Canada is explored by investigating a federal proposal for the devolution of active labour market policies from federal to provincial governments, and by closely examining the positions taken by both levels of government during the development of two federal-provincial labour market agreements in the mid-1990s. The two bilateral agreements chosen for this examination are, the Canada-Nova Scotia Agreement on a Framework for Strategic Partnerships, and the Canada-Alberta Labour Market Development Agreement. The central focus of this research is to examine the extent to which federal and provincial governments’ positions on the devolution of policy are influenced by ‘political’ and ‘public’ interests. The first argument holds that political imperatives influence governmental priorities, attitudes, and motivations as decisions about devolution are made. The second argument maintains that governmental positions on devolution are founded on the motivation to promote the best outcomes for the public at large. This study employs a research focus that is qualitative in nature, and it draws from interpretive and constructivist approaches to inquiry. Interviews were conducted with civil servants who represent federal and provincial interests in the provinces of Alberta and Nova Scotia. A comparative analysis of the evidence found that both political and public interests influenced federal and provincial positions on devolution. This research illustrates that while political and public interests might be separated analytically, in real cases of policy-making they overlap. Nonetheless, the evidence tips the scales towards a political interest explanation much more clearly and convincingly than a public interest interpretation.

Economies of Justice: Workers and Labour Reformers in Late-Victorian Canadian Industrial Fiction - Janes, Daniela Alexandra (University of Toronto, 2004)
In this dissertation I propose the existence of a distinct and previously unacknowledged sub-genre in the Canadian social-reform writing of the 1890s, namely the industrial novel. I concentrate on several late-Victorian Canadian examples: Agnes Maule Machar's Roland Graeme: Knight: A Novel of Our Time (1892), Robert Barr's The Mutable Many (1896), and Albert Richardson Carman's The Preparation of Ryerson Embury: A Purpose (1900). These novels each reflect the expansion of industrial production in the Victorian period and the concomitant social effects of urban industrialism upon the labouring poor. I undertake an examination of these works that analyses the relationship between the novels' middle-class protagonists and the workers whose rights they are defending, seeing in the narrative patterns, imagery, and intertextual references both the articulation of an alternative kind of social justice and a tension emerging between political dissent and political conservatism. These novels of labour unrest caution against violent revolution and instead preach a doctrine of reconciliation and compromise, rooted in a reorientation of conventional notions of justice, a rejuvenation of social institutions, and the imperative of individual moral responsibility. First I focus on Machar's representation of Christian socialism, and how the language of "brotherhood" acts as an antidote and alternative to the morally degenerative effects of industrialism. Machar parallels the labour reform movement to the Christian belief in an afterlife: both are predicated upon faith and deferral, the commission of good works in the present for the benefit of some future blessing. Next, I examine Barr's novel about two strikes in a London factory, looking in particular at issues of leadership and representation. I propose that his novel works to reveal the complexities inherent in any project in which one man must speak for a crowd of others, as the end of the novel amply deconstrates the failure of communication. Finally, in my examination of Carman's novel, I analyse his refashioning of conventional notions of justice. I argue that Carman's narrative suggests the sterility of intellectual debate in the absence of any commitment to social action. I conclude by connecting the late-Victorian Canadian industrial novel to early twentieth-century literary responses to labour advocacy, urbanism, and industrialism.
Keywords: Agnes Maule Machar; Albert Richardson Carman; Industrial fiction; Labor reform; Language; Robert Barr; Workers; literature and linguistics

Analysis of a Worker-Based Participatory Action Research Approach to the Identification of Selected Occupational Health and Safety Problems in Canada Using Mapping - Keith, Margaret Mary (University of Stirling, 2004)
There are limitations to conventional occupational health and safety research approaches and practices and numerous barriers to overcome in order to achieve progress. Occupational health and safety is impacted by the broader social-political environment. Corporatism affects the directions, ideas and practice of regulators, educators, the labour movement, scientists, medical professionals, and society as a whole, thus inhibiting workers' power to influence change. The thesis therefore explores both the wider influences and barriers to occupational health and safety advances, focusing particularly on the Canadian situation, through the general research questions: What has influenced occupational health and safety policies and practices, especially in Canada? What are some of the limitations of conventional occupational health and safety research and practices? To what extent can participatory action research and mapping address identified limitations? These questions are explored from the perspective of the population potentially at risk. New theories and approaches to occupational health and safety research are then applied in this thesis in order to explore a more specific multi-part research question: Can mapping within worker-based participatory action research be used to explore occupational health and safety conditions? In particular, can mapping contribute to occupational health and safety improvements at a local level and beyond; establish workers' previous exposures for compensation purposes; support efforts to bring about justice through compensation for workers affected by unsafe working conditions; and raise worker and public awareness of health and safety? These questions are explored through two different case studies, which examine, in depth, occupational health and safety action and possible remedies. Casino gaming workers in Windsor, Ontario, Canada undertook a collaborative study to investigate and improve current health and safety conditions. Former Holmes foundry and asbestos insulation workers in Sarnia, Ontario, Canada undertook a collaborative study to provide evidence of exposures and ensuing health problems to support claims for compensation. The outcomes of the case studies shed light on the bigger Canadian health and safety picture and demonstrate that mapping as a data collection method used within a participatory action research approach can accomplish a broad range of objectives. Mapping can raise workers' awareness, facilitate communication, build solidarity and cohesiveness, foster community support, mobilise workers to take action to reduce hazards or win compensation, in turn influencing employers, the compensation board and government agencies. The case studies accomplished the shared objective of raising worker and public awareness. The casino workers also gained occupational health and safety improvements and the Holmes workers were successful in gaining compensation.

The Business of Women: Gender, Family, and Entrepreneurship in British Columbia, 1901-1971 - Buddle, Melanie Anne (University of Victoria, 2003)
This study examines female self-employment in British Columbia from 1901 to 1971. Entrepreneurial women comprised a small proportion of the total female labour force but they exhibited differences from the rest of the labour force that deserve attention. The study relies on the Census of Canada to gain perspective on trends in female self-employment over a broad time period; qualitative sources are also utilized, including Business and Professional Women’s Club records, to illustrate how individual businesswomen reflected patterns of age, marital status, and family observed at a broad level. The role of gender in women’s decisions to run their own enterprises and in their choice of enterprise is also explored. While the research focus is British Columbia, this study is comparative: self-employed women in the province are compared to their counterparts in the rest of Canada, but also to self-employed men, and to other working women, in both regions. Regionally, women in British Columbia had higher rates of self-employment than women in the rest of the country between 1901 and 1971. Self-employed women in both British Columbia and Canada were, like wage-earning women, limited to a narrow range of occupational types, but they were more likely to work in male-dominated occupations. Self employed women were also older and more likely to be married, widowed or divorced than wage-earning women; in these aspects, they resembled self-employed men. But there were gender differences: whether women worked in female or male-dominated enterprises, they stressed their femininity. The need to take care of their families, particularly if they had lost a spouse through death or desertion, provided additional rationale for women’s presence in the business world. Family, marital status, age, gender and region all played a role in women’s decisions to enter into self-employment between 1901 and 1971.

The Search for Solidarity: The Industrial and Political Roots of the Cooperative Commonwealth Federation in British Columbia, 1913-1928 - Isitt, Benjamin (University of Victoria, 2003)
Born out of the industrial and political struggles of organized labour at the end of the First World War, the BC CCF was a product of organizational and ideological conflict in the 1910s and 1920s. This study explores the shift of BC socialism towards industrial action, which culminated in the One Big Union and the sympathetic strikes of 1919. It then examines the emergence of anti-Communism on the Left, shaped by the experience of political unity and disunity during the 1920s. These two factors fundamentally influenced the ideology and strategy adopted by the Cooperative Commonwealth Federation (CCF) in British Columbia. The ideological and tactical divisions of the 1930s were contested during the 1910s and 1920s. The collapse of the One Big Union, combined with deteriorating relations with the Communist Party, shifted BC socialists away from industrial militancy and toward parliamentary forms of struggle.

Searching for the Springs of Health: Women and Working Families in Winnipeg's 1918-1919 Influenza Epidemic - Jones, Esyllt Wynne (University of Manitoba, 2003)
In the winter of 1918-1919, a pandemic of influenza crossed the globe, killing as many as 50 million people. This dissertation is a local study of influenza in Winnipeg, Canada. It dissects the social responses to the disease from four different perspectives: that of the public health and medical authorities; middle class Anglo-Canadian women volunteers who provided nursing care and material relief to the city's poorer influenza victims; working class and immigrant families; and organized labour. The dissertation argues that the influenza epidemic, coming on the heels of the devastating Great War, and arriving in the midst of class, ethnic, and gender conflicts, played a role in deepening the social cleavages of Winnipeg society in the period, particularly those of class and ethnicity. Class and ethnic tension was not the inevitable outcome of the epidemic. Rather, it was the result of the social inequality of the disease's impact–working families represented a disproportionately high number of influenza's victims–and the failure of public authorities to mount a compassionate and cooperative community effort to fight the disease. The volunteerism of middle class Anglo-Canadian women, too, failed to build the bonds of community. Labour believed that the state response to influenza was a betrayal of principles of justice and public good. Workers' families bore the brunt of public closures and layoffs. A spirit of mutualism sustained families and neighbourhoods through the disease, and contributed to the mobilizing successes of the workers' movement in 1918-1919. The trauma of the epidemic suggested the fragility of the social order, and workers' capacity to build an alternative society. Their vision of social transformation included the creation of the "springs of health": a living wage, quality housing, and equal access to a democratic medical system. Many working families, nevertheless, found it difficult to recover from the loss of spouses and children. Their stories suggest that influenza had a long-term impact upon the evolution of post-war Canada that we are only just beginning to understand.

Divided We Stand: A Study of the Development of the Conflict Between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury, Ontario (1942-1969) - Miller, Jason A. (McMaster University, 2003)
During the height of the Cold War, a new form of conflict among Canadian workers emerged along political lines. In some cases, the major source of conflict shifted from that of union versus management to left-wing union versus right-wing union. This thesis focuses on such an inter-union battle between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury, Ontario from 1942 to 1969. ln this analysis, which attempts to incorporate the perspectives of the unions, the mine operators, and the Catholic Church and its affiliate organizations, it will be shown that despite the profound influence of the union executives, the media, the Church, and other prominent figures, the final decision regarding which union to join was ultimately made by the rank-and- file members at Inco and Falconbridge (with the miners at Inco choosing the Steelworkers as their bargaining agent while the miners at Falconbridge chose to remain with Mine-Mill).
https://macsphere.mcmaster.ca/bitstream/11375/12227/1/fulltext.pdf

Workers, Labour Unions and the Law: Canadian Labour Unions in the New World of Bilateral Freedom of Association - Sauve, David (Carleton University, 2003)
What are the consequences for the Canadian Labour movement in holding contradictory positions concerning freedom of association? The research into this question conceptualizes Canadian unions as partners with capital and the state in a legally constructed regime of labour relations and collective bargaining. Pertinent Supreme Court of Canada cases concerning labour unions and freedom of association demonstrate that labour unions are inconsistent in their claims concerning freedom of association. This study reveals that while labour unions claim freedom of association is unilateral, that is, workers do not have a right to dissociate, the courts have found that freedom of association is bilateral and workers have a constitutional right to not associate or associate with whom they choose. To date, the courts have also found that infringing on workers' freedom of association is justified under the 'Charter'. However, in the future, the courts may well find these infringements are not justified.

Bankers and Bomb Makers: Gender Ideology and Women's Paid Work in Banking and Munitions During the First World War in Canada - Street, Kori (University of Victoria, 2003)
During the First World War, some Canadian women found themselves in new and unfamiliar environments, doing jobs apparently unavailable to them before the war. Many of those women were successful in the new opportunities available to them. The focus of this study is twofold. First, it examines the scope and the nature of women's work in two industries, banking and munitions, during the war. This is an important step because we still know very little about women's experience of the war. Understanding how many women worked and in what capacity is essential to understanding the nuances of women's wartime experience. Women who worked in banking and munitions were not a homogeneous group. The composition of the wartime workforce is also analysed. The war's impact on wage rates for women is also examined. Second, the study focuses on the nature of the impact of wartime participation on gender ideology. In particular, the study seeks to determine if gender ideology was affected by women's expanded opportunities in masculine occupations during the war. Often, the historiography regarding women and war is characterised by a binary discourse that seeks to determine whether on not wars liberate women. Rather than engage in that debate, this study attempts to avoid it as much as possible. Women's experience of the war in these two industries was complex. The study explores how women could both challenge and reaffirm ideas about gender; how attitudes towards and about women could change and remain the same; and how employee and employers alike strove to undermine and maintain the sexual division of labour and labour processes that were threatened by the entrance of large numbers of women into jobs defined as men's work. Women's participation both challenged and reinforced traditional notions about gender. Essentially, despite being successful ‘bankers’ women remained unsuitable for a career in banking. Similarly, regardless of their participation in munitions factories, metal shops remained no place for women. Quantitative, oral interview and qualitative sources including contemporary newspapers and magazines, were used. In particular, a great deal of the evidence was derived from several databases constructed for this project.

Class, Politics and Social Change: The Remaking of the Working Class in 1940s Canada - Camfield, David (York University, 2002)
This interdisciplinary dissertation aims to develop social and political theory capable of understanding social class as a structured process and relationship mediated by gender, race and other social relations and taking place in time and specific socio-material contexts, in order to analyse working classes as historical formations. It also aims to use this perspective and the existing body of historical scholarship to conduct a theoretically-rigorous study of the remaking of the Canadian working class in the 1940s. Arguing that recent theoretical work on class formation is inadequate, the dissertation critically appropriates ideas drawn from classical and contemporary scholarship to outline a theory of working classes as historical formations. An account of how dominant classes exercise power in capitalist societies is a necessary complement to this theory; the overview developed theorizes the existence of capitalist rule in differentiated forms and as inherently, but not primarily, ideological. From this perspective, the dissertation analyses the remaking of the Canadian working class in the paid workplace, community and household spheres in the 1940s. It argues that between 1941 and 1947 a broad but uneven process of class recomposition took place, focussing on such issues as the character of struggles in this period, their participants, their organizations and ideologies in order to illuminate the dynamics of change in working-class formations. In the course of struggle, both the working-class formation and capitalist rule were altered in important ways. The new formation that stabilized in the late 1940s featured improved living standards and greater unity against capital at the most elementary level. It was also shaped in important respects by a particular configuration of racist, sexist and heterosexist social relations. Unions changed from within and without, becoming generally committed to a responsible and bureaucratic practice. The CCF became the undisputed party of the English-Canadian workers' movement, weakening and marginalizing political radicalism. Although it is misleading to interpret this as working-class incorporation, working-class capacities to change society had been constrained and undermined in new ways, in part as a result of the very reforms workers wrested from employers and state power.

The Political Economy of Indian Health and Disease in the Canadian Northwest - Daschuk, James W. (James William) (University of Manitoba, 2002)
The dissertation identifies the origins of the present disparity of health conditions between Indian communities and mainstream society in western Canada. It examines the relationship between economics and health of Indian populations in the Canadian northwest from the early eighteenth century to the end of the nineteenth century. It documents the development of the fur trade in relation to changes in the geographical distribution of aboriginal societies resulting from the differential impact of introduced European diseases. For a period of one hundred and fifty years, infections that came as a consequence of trade were the primary source of mortality due to illness among First Nations. In addition, social pathologies resulting from European trade strategies affected the well being of communities in the northwest. Climate and environment contributed to the differential success of many groups integrated into the global economy through the fur trade. Canada's acquisition of the northwest changed this pattern. Its commitment to the terms of Treaties opened the west for agricultural development and settlement. The Dominion's development strategy, the National Policy, coincided with the extinction of the bison, undermining the ability of plains Indians to compel the government to deliver on their Treaty commitments. To facilitate the implementation of its economic and political order, the Dominion used its famine relief strategy as a means to subjugate them. By the early 1880s, tuberculosis emerged as a full blown epidemic among the Indians of the plains. The spread of tuberculosis through the Indian population of the plains was the result of the protracted period of malnutrition. Punitive measures imposed after the brief armed resistance to Dominion hegemony further weakened the population already largely infected with the disease. Severe mortality weakened the population already largely infected with the disease. Severe mortality resulted from the spread of acute infectious disease among the compromised population. Within fifteen years of signing Treaties many plains populations declined to their demographic nadir.

The Engineering of an Enemy: The Catholic Church, United Steelworkers, Canadian Labour Congress, and International Union of Mine, Mill, and Smelter Workers Local 598 - Enoch, Simon (McMaster University, 2002)
As global politics realized a fundamental realignment with the end of the Second World War, the Canadian state desired the formation ofa national consensus over its newly developed Cold War policies. It set about this task through the use of anti-communist rhetoric to facilitate a repressive and intolerant atmosphere where dissent of state policies could be identified as subversive and dangerous. In promulgating this Cold War ideology, Ottawa was wary of the illiberal approach that characterized American McCarthyism. Rather, Ottawa adopted a strategy of "privatizing" its anti-communism through the use of extra-state actors. By "farming" out its repressive activities, Ottawa could portray itself as a neutral defender of liberal values, while at the same time facilitating a climate of repression that would further its policy aims. Attendant to this, the extra-state actors used this state facilitated framework in order to advance their own interests and agendas. This strategy was starkly illustrated by the USWA raids against IUMMSW Local 598 in 1962. The interests of the state, the Catholic Church, CLC, and USWA coalesced around the elimination of Mine Mill local 598 as a representative of miners in northern Ontario. The Catholic Church sought the elimination of a progressive secularizing force in the Sudbury community that threatened the Church's institutional reproduction. For Steel, the acquisition of over 17,000 dues-paying members and the elimination ofIUMMSW as a competitor in the membership rich northern Ontario mining communities. While the state prospered from the virulent anti-communist environment and the elimination of a potentially militant union from control over the largest source of nickel in the non-Communist world. Thus the boundaries demarcating the state from civil society are less clear than some would have us believe. The USWA/Mine Mill events illustrate the nuance in the relationship between the state and private actors in the mobilization of ideological hegemony.

Representing Vancouver’s Working Girls, 1890-1930 - McMaster, Lindsey (University of British Columbia, 2002)
My dissertation addresses representations of the young women of Vancouver's working class, who, in the first part of the twentieth century, became touchstones for judgements on city life, work, and morality. Young, single, wage-earning women were something new and troubling to the middleclass administrators and social critics of the time. While the city's numerous single working men, with their overcrowded dwellings and tendencies to unionize, were considered somewhat disorderly, the necessity of their presence was never questioned. "Working girls,"on the other hand, seemed to embody all that was unnerving and unnatural about modern times: the disintegration of the family, the independence of women, and the promiscuity of city life. These kinds of anxieties were not unique to Vancouver: the issue of wage-earning women was deemed a "social problem" in various western cities. But Vancouver's singular geopolitical situation meant that these anxieties were exacerbated and amplified in distinct and curious ways. In 1922, for instance, a law was passed "for the protection of women and girls" which prohibited white women from working alongside Asian men. What combination of racism, paternalism, and moral panic gave rise to such legislation? And how did the women react to being controlled and judged by such assumptions? Rather than viewing the problems of wage-earning women as coextensive with those of working men - problems of wages, working conditions, and workers' rights - social administrators and reformers focussed largely on the moral implications of women's entrance into the workplace, particularly insofar as it represented a break from traditional Victorian ideals of domestic femininity. Denied the recognition afforded male workers as members of the labour force and economic agents, working women suffered various disadvantages in the workplace, their wages barely enough to survive on, and their rights as workers ignored by employers and union leaders alike. The tendency in historical accounts of Canada to overlook or underestimate the importance of women's work is undoubtedly in part due to the ideological disinclination to see or to represent women as workers rather than as wives and mothers. This is why my analysis focusses on the politics of gender and representation, for it is through representational conventions that women were pressured to embody a traditional domestic role, and likewise it is through a representational agenda that women were denied recognition as valuable workers.

Cross-Movement Coalitions and Political Agency: The Popular Sector and the Pro-Canada/Action Canada Network - Bleyer, Peter (London School of Economics and Political Science (LSE), 2001)
Through a historical account of the Pro-Canada/Action Canada Network (PCN/ACN), this dissertation examines coalition formation among social movements. It argues that the complex process of cross-sectoral coalition formation and thus the potential for convergence of social movements can best be understood by combining elements of different analytical frameworks. This dissertation draws on elements of the two dominant paradigms for the study of social movements, resource mobilization theory and new social movement theory. Specifically, it utilizes the formers' attention to the specifics of organization and structure and the latter's focus on the discursive formation of identities. Both are then combined with the uniquely Canadian but theoretically underdeveloped concept of the popular sector and a neo-gramscian perspective on social formation and mobilization that draws on political economy and class-analytical traditions. With its formation in 1988 around opposition to the Canada - U.S. Free Trade Agreement, the PCN/ACN was an early example of a broader trend for trade and investment to become key arenas for social and political contention at the turn of the century. This dissertation challenges the assumptions of most analytical frameworks concerning the limits to coalition formation and argues that the nature of the unifying issue is an important determinant of the potential for the growth and deepening of social alliances. After reviewing the historical conjuncture in which the PCN/ACN emerged, this dissertation traces the history of key sectors and member organizations - labour, women and ecumenical justice - paying specific attention to their approach to political engagement and the issue of free trade. As a result, it establishes the necessary background to understand both the initial basis for unity and the Network's progression beyond a lowest common denominator alliance around a single issue, to a broader mandate. This dissertation provides empirical evidence on which to judge the potential of social movements to displace other discourses and agencies on the left. Given the contemporary interest in the role of social movements, NGOs and civil society, this dissertation provides some essential signposts for two types of practitioners: academics seeking to understand outcomes and activists hoping to determine them.

A House Like No Other: An Architectural and Social History of the Ukrainian Labour Temple, 523 Arlington Avenue, Ottawa, 1923–1967 - Hunchuck, Suzanne Holyck (Carleton University, 2001)
Traditional architectural histories of Canada have tended to define the Ukrainian architectural presence only in terms of the sacro-religious or the rustico-picturesque. The more complex reality—that of the community's secularity, urbanity, and proletarianization throughout its history—is demonstrated by a third building type, the chytalnia or reading room, of which a Labour Temple is a socialist/pro-communist variant. These institutions were often found in urban centres where they were frequently located in industrial vernacular houses. Their study therefore confounds conventional notions of Ukrainian piety and rusticity, of a historical geography that consists exclusively of rural Prairie settlement, and of formalist paradigms regarding architectural form. Similarly, the architectural history of Ottawa has been predicated upon monumentality and picturesque settings to the neglect of regional vernacular forms, as well as upon a bilingual/bicultural ethnoculture that negates the polyethnic nature of the city. This study posits the Ottawa Ukrainian Labour Temple as a case study for exploring the limitations of traditional historiography regarding vernacular architecture, Ukrainians in Canada, and industrial vernacular housing in Ottawa.
Keywords: Communication and the arts; Ontario; Social sciences

On the Hook: Welfare Capitalism on the Vancouver Waterfront, 1919-1939 - Parnaby, Andrew (Memorial University, 2001)
In 1923, after nearly three decades of class conflict on the Vancouver waterfront, the Shipping Federation of British Columbia, an umbrella organization of shipping, stevedoring, and warehousing interests, undertook a far-reaching agenda of welfare capitalism. Drawing on wider currents of progressive reform which were cresting in the interwar period, and inspired by the example set by its counterpart in Seattle, the Shipping Federation created new joint political structures, adopted a range of paternalist initiatives, and decasualized the waterfront workplace. From its vantage point, this was a "good citizens" policy, and it was designed to: build bridges across the class divide, gain greater control of the work process, stave off the intervention of unions and the state, and, in the end, mould a more efficient and compliant waterfront workforce. The creation and implementation of this reform agenda, the ways in which white and aboriginal waterfront workers negotiated the politics of paternalism and labour market reform, and the long-term ramifications of this dynamic are at the core of this thesis. – Welfare capitalism shaped patterns of life and labour on the waterfront significant ways: informal ways of regulating the workplace atrophied; labourism was revived; and some waterfront workers acquired a reasonable standard of living. The trade-off at work, here, was this: only those employees who divested themselves of more radical political sensibilities, and adhered to waterfront employers' broader vision of an efficient, decasualized workplace, could hope to secure a living wage and fulfill their obligations as breadwinners, husbands, and citizens. For aboriginal longshoremen, most of whom were from the Squamish First Nation, this bargain was especially difficult to negotiate for it came freighted with the additional challenges associated with being "Indian" in a white society. Unlike their white counterparts who passed muster, they were marginalized from the waterfront during this time as decasualization's new time-work discipline conflicted with their more traditional sensibilities and ongoing need to work at a variety of tasks to ensure material and cultural survival. – Straddling labour history, aboriginal history, and the burgeoning literature on law and society, this thesis rejects conventional interpretations of welfare capitalism that conceptualize it as either a failed experiment in industrial democracy, or a drag on the emergence of the welfare state. In doing so, it re-positions welfare capitalism in the context of the wider return to normalcy following the Great War, and the powerful reform impulses that took aim at family, citizen, and nation. Rather than forestalling the welfare state, this citizen-worker complex–which manufactured a new sense of entitlement amongst white waterfront workers–was part of a broader cultural shift that would, after the trials of the Great Depression and challenge posed by the Communist Party of Canada, eventually underwrite the state's very expansion. On a broad level, then, this analysis illustrates how the prevailing liberal-capitalist order was successfully rehabilitated after the Great War and 1919, and how, in the long-term, it successfully contained, by consent and coercion, those forces which were antithetical to the prevailing economic and political status quo.
Keywords: British Columbia; Labor market reform; Paternalism; Social sciences; Vancouver; Waterfront; Welfare capitalism

"And There's Nothing Goes Wrong": Industry, Labour, and Health and Safety at the Fluorspar Mines, St. Lawrence, Newfoundland, 1933-1978 - Rennie, Richard Charles (Memorial University, 2001)
In 1933, an American entrepreneur offered the people of St. Lawrence, a small town on the south coast of Newfoundland, the prospect of escaping rampant unemployment and meager public relief by starting a mine to extract the area's vast deposits of fluorspar, which is used in the manufacture of steel, aluminum, and various chemical products. Coming in the context of the Great Depression and the collapse of the fishing industry, the mining industry was eagerly embraced by residents of St. Lawrence and surrounding communities. Several mines were subsequently established, by both the original American company, the St. Lawrence Corporation of Newfoundland, and later by the Aluminum Company of Canada (Alcan). The fragile prosperity that accompanied the industry from the 1930s until closure of the last Alcan mine in 1978, however, exacted a heavy price. Many St. Lawrence workers lost their lives to industrial diseases caused by dust and radiation in the mines. – This thesis explores the history of industry, labour, and health and safety at the St. Lawrence mines. This study focuses on the struggle by workers and their union for recognition of workplace hazards, improved working conditions, and adequate compensation for industrial disease victims and their families. The thesis argues that, rather than being passive victims of an unavoidable tragedy, workers at St. Lawrence were aware of the adverse health impacts of their work from the very early years of mining, and fought constantly over several decades to have their concerns addressed. Furthermore, the thesis argues that the disaster which ultimately unfolded at St. Lawrence was primarily the result of industry and government authorities ignoring or downplaying legitimate concerns and thereby shirking their moral and legal responsibilities.

Disorganized Labour: Canadian Unions and Constitutional Reform - Savage, Larry (Brock University, 2001)
Constitutional reform dominated the Canadian public policy agenda during the 1980s and early portion of the 1990s. As a pressure group operating within a federal system, the Canadian Labour Congress (CLC) has been unable and unwilling to confront the issue of constitutional reform. The CLC's confederal structure, combined with its political relationship with the New Democratic Party (NDP), has prevented the CLC from acting as a progressive force for positive constitutional change. Ideological and philosophical differences between the Quebec Federation of Labour and the NDP convinced the CLC to remove itself from the patriation debate in the early 1980s. Labour's short-sighted non-involvement in the process of patriating the Constitution eliminated the possibility of having collective rights enshrined in the Charter of Rights and Freedoms. Subsequently, the Supreme Court of Canada ruled that the right to strike and bargain collectively were not constitutionally protected. The Meech Lake and Charlottetown Accords provided organized labour with a renewed opportunity to promote a pro-union, class-based, constitutional rights discourse, but the CLC's internal cleavages over language, region, and identity, once again, proved too powerfiil a force to overcome. The Canadian labour movement's vision of social justice and economic equality has been obstructed by its unwillingness to adequately confront divisive constitutional issues. However, in an era of rights discourse and neo-liberalism, constitutional reform may provide organized labour with the best opportunity to have its voice heard.

"The Hand that Rocks the Cradle Rocks the World": Women in Vancouver's Communist Movement, 1935-1945 - Thorn, Brian T. (Simon Fraser University, 2001)
The period between 1935 and 1945 was a key one for the Communist Party of Canada [CPC or CP] due to the tumult of the Great Depression and the Second World War. Women were key players in the success that the CPC had during this period, one in which Communist and other left-wing movements grew and were more 'respectable' than they were during the Cold War that would follow. Yet women were secondary players in the Communist movement in Vancouver. While CP women played crucial roles in raising money for the Party, setting up fighting organizations such as the Vancouver Housewives league, and supporting the Allied war effort, CP members of both sexes pushed Party women into more traditional 'feminine' roles of wives, mothers, and ornaments. The Vancouver Communist Party offered a substantial challenge to Canada''s liberal state and the CP provided radical women with an outlet to channel their abilities against capitalism. In the end, however, the CP failed to alter substantially the fundamental division of labour between radical men and women. Communists upheld the mainstream doctrine of "separate spheres": they believed that men were workers, labour organizers, and producers while left-wing and working class women were domestic, passive, and consumers. This thesis concludes that while we cannot expect radical organizations to be completely separate from the gender ideals of the period in which they existed, the CPC did little to challenge traditional gender roles.

" Getting a Grand Falls Job": Migration, Labour Markets, and Paid Domestic Work in the Pulp and Paper Mill Town of Grand Falls, Newfoundland, 1905-1939 - Botting, Ingrid Marie (Memorial University, 2000)
While it has been generally understood that domestic service was an institution of particular importance to working-class women and to middle-class householders in North America in the late 19th and early 20th centuries, we still know little about the interwar years, a period during which the occupation declined in overall importance, but still defined many women's working lives. In the 1920s and 1930s, a vast majority of women who grew up in Newfoundland's coastal communities, where household production and the family fishery remained the mainstay of the economy, spent part of their lives performing domestic tasks for pay. To begin to understand the historical and cultural significance of domestic service to women's lives in Newfoundland, this dissenation uses a case-study approach. It focuses on the pulp and paper mill town of Grand Falls, where there was a steady demand for domestics by mill workers and their families, the town's elite, and hotels and boarding houses during the 1920s and 1930s. One of a number of single-resource towns supported by Newfoundland's economic diversification policies of the late 19th and early 20th centuries, Grand Falls was built in the interior of the island by the Harmsworth brothers of Britain in 1905. By tracing domestics' lives and experiences from countryside to company town, into the household = as workplace - and then into their married lives, the study explores themes relating to the gendered nature of uneven development. For instance, many Grand Falls employers shared much in common with the women they hired, in terms of religion, ethnicity and social origin., which raises interesting questions about the gender and class dimensions of an employer/employee relationship that has traditionally been characterized as one of domination and subordination. It also considers that relations of gender and class within the company town were formed in conjunction with factors such as migration patterns, pre-existing concepts of the gender division of labour within household production, company paternalism and social stratification within the workplace, the household and the town. The ways in which these factors overlapped and shaped the lives of domestics forms the backdrop of this study.

Le mouvement ouvrier montréalais, 1918-1929 : structure et conjoncture - Dansereau, Bernard (Université de Montréal, 2000)
Cette thèse traite de l'évolution du mouvement ouvrier montréalais de 1918 à 1929. Nous examinons les diverses organisations ouvrières, tant leur structure et leur composition, que les différentes idéologies qui coexistent dans les groupes ouvriers de la région montréalaise. Après avoir retracé les origines de ces organisations, leur évolution au cours de la Première Guerre mondiale, nous analysons leur développement au cours de la décennie qui suit la fin guerre. Nous cherchons, au delà des présupposés et des généralités, à comprendre le processus d'évolution du mouvement ouvrier montréalais. L'analyse de l'évolution des syndicats et des organisations politiques permet de saisir toute la complexité de rapports sociaux et les difficultés pour les travailleurs d'occuper une place significative. Notre analyse décrit aussi la place des diverses composantes nationales présentes dans le mouvement ouvrier montréalais. Nous insistons sur la place des travailleurs francophones et sur le rôle des travailleurs juifs jusqu'ici méconnu. Nous subdivisons cette tranche historique en trois périodes qui recoupent des conjonctures spécifiques. Les années de l'immédiat après-guerre sont marquées par une très forte agitation ouvrière alors que de très nombreux ouvriers et ouvrières se dotent de syndicats et revendiquent de meilleures conditions de vie et de travail. Le syndicalisme international de métier voit sa prédominance contestée par le syndicalisme canadien et le syndicalisme révolutionnaire. À droite de l'échiquier syndical, le syndicalisme catholique s'installe définitivement au Québec et constitue une des caractéristiques majeures du mouvement ouvrier québécois. L'effervescence ouvrière ne débouche pas sur des organisations politiques fortes malgré l'existence d'un parti ouvrier qui obtient quelques gains électoraux alors que les organisations de gauche doivent se réorganiser, victimes notamment de la répression gouvernementale et patronale. La crise, qui s'enclenche dès le milieu de 1920, affecte considérablement des organisations ouvrières lorsque le capitalisme tient à revenir aux situations qui prévalaient avant la guerre. Les organisations syndicales cherchent à résister à cette stratégie mais le nombre de syndicats décroît. Toutefois, cette baisse du membership syndical ne ramène pas le nombre de syndiqués au niveau de 1913 parce que, parmi les syndicats apparus dans la foulée de la révolte ouvrière, de nombreux syndicats résistent efficacement, dont des syndicats canadiens et des syndicats catholiques. La gauche se réorganise autour du Parti communiste canadien, creusant un fossé entre eux et le reste des militants ouvriers. Le Parti ouvrier du Canada entreprend sa lente marginalisation. Au milieu de la décennie, profitant d'une reprise économique, le mouvement ouvrier se relève. Les syndicats se réorganisent, leur membership augmente et leurs revendications deviennent plus offensives montrant ainsi un regain de militantisme. Mais les divisions s'accentuent dans les rangs syndicaux alors que les syndicats canadiens et catholiques contestent de plus en plus le leadership occupé par les syndicats internationaux de métier. Au plan politique, le Parti communiste occupe pratiquement toute la place, les socio-démocrates se voyant relégués à quelques bastions.
https://doi.org/1866/28793

The New Democratic Party and the Union Vote. - Dowler, Kevin John Gordon (University of Windsor, 2000)
The following study examines the NDP and the union vote. The NDP and labour unions have been officially linked since the NDP's formation in 1961. Despite the initial optimism of the NDP-labour link, the change from the CCF to the NDP has resulted in limited electoral success, especially at the federal level. The partnership between labour and the NDP has met with limited electoral fortunes. Although their tendency to vote NDP is higher than that of other groups, the vast majority of union members still vote for other parties. Federal election studies have repeatedly shown that 10 percent of non-union members, 20 percent of union members, and 30 percent of NDP affiliated union members vote for the NDP. The question is why do the remaining 70 to 80 percent of union members fail to vote for the NDP. This study aims to address this problem using survey research. The first chapter reviews the link between the NDP and labour and voting determinants in Canada. The second chapter looks at the research design and methodology of this thesis. Chapter three and four examines the results of the statistical analysis. Finally, chapter five summarizes with a discussion and concluding remarks.

Devenir seigneur en Nouvelle-France: mobilité sociale et propriété seigneuriale dans le gouvernement de Québec sous le régime français - Grenier, Benoît (Université Laval, 2000)
Analysant la mobilité sociale dans le gouvernement de Québec sous le Régime français, ce mémoire aborde la propriété seigneuriale en tant qu'illustration de la promotion sociale dans la vallée du Saint-Laurent au XVIIe et au XVTIIe siècle. Cette analyse, portant sur une soixantaine d'individus aux origines modestes, issus notamment de la paysannerie, ayant accédé à la propriété seigneuriale, se veut une contribution a l'étude de la promotion sociale en Nouvelle-France. Quatre parties constituent l'essentiel de ce mémoire. L'origine de ces individus et les modes d'élévation sociale sont étudiés dans une première servant de cadre contextuel et de présentation sociodémographique. Les trois chapitres suivants visent à répondre plus directement à la problématique de l'étude, à savoir l'impact socio-économique de la propriété seigneuriale chez ces seigneurs aux humbles origines. La durabilité de la propriété seigneuriale, ainsi que le fait d'y résider ou non et le peuplement de la seigneurie sont les éléments étudiés dans le deuxième chapitre. Le troisième chapitre aborde la question du prestige tributaire de la seigneurie, en s'intéressant aux appellations attribuées aux seigneurs, de méme que les fortunes seigneuriales, pour connaître l'incidence économique de la propriété seigneuriale. Dans un dernier temps, le quatrième chapitre met en relief les alliances matrimoniales des familles seigneuriales, également révélatrices du possible impact de la possession d'une seigneurie. Au sein de cette société française d'Ancien Régime, transplantée sur les rives du Saint- Laurent, d'importantes mutations s'opèrent. L'une de ces transformations est perceptible par la plus grande possibilité de mobilité sociale, quasi inexistante en France. Par l'analyse des destins d'hommes dont la naissance ne laissait en rien présager un tel parcours, ce mémoire vise a comprendre l'enjeu de la propriété seigneuriale pour de tels individus ainsi que ses répercussions.

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (McGill University, 2000)
The everyday life of people on the street has not received the attention it deserves in the history of late nineteenth and early twentieth-century Quebec. This dissertation joins a small number of recent studies which redress this omission. It makes a significant contribution to existing examinations of North American cities and Canadian social history through the use of categories which are rarely employed and questions that are seldom posed in investigations of working-class history during the period of industrialization. A holistic treatment of Marxist philosophy provides the theoretical underpinnings for a sensitive engagement with daily street life in an urban milieu. As a site of intense sociability, Notre-Dame Street, the main street of the industrial suburb of Saint-Henri, offers a unique perspective on the intricate use of public space and its relations to social space. This thesis covers the period between the years of town incorporation in 1875 and annexation to the City of Montreal in 1905. Notre-Dame Street underwent significant transformations in this period. A main street of a small town on the outskirts of Montreal became the principal commercial street of a bustling industrial city. The 1890s was a decade of particularly marked shifts, characterized by significant population growth and dramatic changes in physical form. Class and ethnic tensions intensified as a result. A 1891 labour dispute at Merchants Manufacturing, a textile factory, took to the streets, and the local elite contested George A. Drummond's refusal to pay municipal taxes in 1897. Resistance to monopoly control of utilities was evidenced by the use of petitions and protets or notarized letters. Workers' parties, journalists, and municipal reform leagues increasingly challenged the hegemony of the local elite whose persistent practices of overspending resulted in a substantial debt and annexation. The study of a local street in an industrializing community demonstrates the prevailing social and political distribution of wealth and power. It reveals significant differences between the various class ideologies which were played out in the management of the public space of the street. An economic liberal ideology was instrumental to the development of the modern Western city through the creation of divisions between public and private spaces. Social usage, the visible presence of the working and marginal classes and women on city streets, suggests a different reality. A reconstruction of daily street life from a diversity of written and visual sources indicates that women, men, and children inhabited and frequented homes, shops, and offices, travelling to and from work, and various places of recreation. The rhythm of everyday street life was punctuated by unusual events of a celebratory, criminal, and tragic nature, which emphasize the connections between spatial structures and subjective experience. The local management of public space thus involved class antagonisms, characterized by negotiation, transgression, and resistance. This dissertation argues that the politics of this public space benefited the class interests of a grande bourgeoisie of Montreal and a local petite bourgeoisie, to the detriment of the working classes. These conflicting class interests were played out in a variety of different ways. The exclusion and appropriation of social and symbolic spaces were characterized by distinct property ownership and rental patterns. An anglophone grande bourgeoisie of Montreal owned vacant and subdivided lots. A francophone petite bourgeoisie dominated property ownership, and a majority of renters lived in flats on the main street and on adjoining streets. The shaping of the physical infrastructure was distinguished by the growth of monopolies and minimal local intervention. The civic manifestation of the ordered and ritualistic celebration of the parade emphasized a Catholic identity. Attempts to impose an appropriate and genteel code of behaviour on city streets led to the moral regulation and social control of criminal behaviour.
OCLC: 56684820
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Leadership and Staff in the Union of Northern Workers from 1967 to 1996 - Powell, Christopher William (Memorial University, 2000)
The Union of Northern Workers, known as the Northwest Territories Public Service Association prior to 1987, is the largest labour union in the Northwest Territories. Northern labour is a little explored field in Canadian history, and as such, this work surveys new ground. Trade unionism in the North's private sector began at the close of the Second World War. The UNW, however, like most public sector unions in Canada, had its roots in the 1960s. This study examines issues pertaining to the union's leadership and staff from 1967, when correctional workers in Yellowknife first organized, until the 1996 convention, when the union took steps to divide into two separate unions in anticipation of the creation of Nunavut in 1999. From its start, the union's geographic jurisdiction distinguished the UNW as unique among Canada's public service unions. It and its predecessor, the NWTPSA represented workers in Canada's most northern reaches. The challenges of life in the North were as real for the union as they were for its members. A relatively small membership spread across such a huge land mass presented obstacles with regards to leadership and service. Also, cultural factors differentiated the organization from others. With an increasing native membership, mostly Inuit, lnuktitut became the union's second language. Distinguishing the union institutionally was its component status within the Public Service Alliance of Canada. The quality of the relationship between these two bodies regularly fluctuated between excellent and belligerent. Similarly, the union's relationship with the Nonhwest Territories Federation of Labour degenerated from founding member to pariah status, in spite of the UNW comprising the overwhelming majority of the Federation's membership. As the union grew from a fly-by-night, seat-of-the-pants organization of less than 100 members at its inception, to over 5,000 when it divided, leadership and staffing gained increasing importance. To meet the challenges of representing northern workers, the union increasingly attempted to professionalize its leadership cadre. The effect of this was an increasing distance between members and leaders which ultimately resulted in the secession of the Nunawt membership.
Keywords: Northwest Territories; Social sciences

"Support Pending": The Canadian Autoworkers' Struggle for Adjustment Assistance at a Time of Industrial Change, 1960-65 - Roy, James A. (Carleton University, 2000)
In 1960 the Canadian United Auto Workers suggested to the government that in order to save the automobile industry, rationalization with the American industry was a viable and desired option. Over the next five years, as the government gradually moved towards integration, the union stood behind the principle, yet at the same time stated tha protection for dislocated and laid-off workers must be part of the deal for union support to be forthcoming. The union, which felt that the costs of government-induced layoffs should be fully borne by the state, did not waver in its commitment to securing safeguards, even though from 1960 to the Auto Pact in 1965 it became increasingly apparent that the granting of adequate protection was not on the government's agenda. The layoff of 1,600 workers in 1965 resulted in the withdrawal of Canadian UAW support for the trade deal and highlighted the significance and importance of the over-riding condition of support, the protection of workers from the consequences of state actions.

Deploying Discourses of Employability and Domesticity: Women's Employment and Training Policies and the Formation of the Canadian Welfare State, 1935–1947 - Stephen, Jennifer Anne (University of Toronto, Ontario Institute for Studies in Education, 2000)
The period 1935 to 1947 provides an excellent opportunity to investigate the ways in which the employment and training policies of Canadian welfare state forms delineated the boundaries of gender, race, class and nation in ways that actively constituted (il)legitimate social and economic forms of work, of motherhood, of sexuality and citizenship. Covering attempts starting in the Depression and accelerating during the Second World War into the postwar period, this study tracks the constitution and deployment of government attempts at mapping the female labour supply, of monitoring the activities of women in the labour market, of charting and opening up to scrutiny the conditions of women's labour force attachment: all in an effort to predict and prescribe patterns of women's employment and problems of female unemployment. I approach government reports, studies, commissions and committees as policy events—exercises in governance—as markers for policy analysis which signified important shifts in governmental approaches to the phenomenon of female participation in the formal waged economy. Viewed during the war as a crucial national resource, central to the war effort, women war workers would be cast as a largely ‘unskilled female labour reserve’ by war's end. I examine how ideas about mental testing, intelligence and human capacities—ideas that comprised the foundation of the mental hygiene programme during this period—informed employment and training policies in the formation of the Canadian welfare state for the period 1935–1947. During the Depression, studies of the labour force produced classifications of unemployed women and men. Scrutiny of female employment patterns resulted in the production of categorical knowledges about employability. These practices were further elaborated through the unprecedented research opportunities presented by the war. Suitable vocation, aptitude, and measures of intelligence: these concepts were drawn upon as part of a growing apparatus of employment policy intended to facilitate the smooth transition into the postwar period. I argue that the roster of policies and programmes devised in the name of postwar rehabilitation constituted ideas about female employability which were deeply imbued with the principles of scientific racism and sexism at the core of the mental hygiene program. Vocational planning, counselling and training practices reorganised relations of employment and of unemployment in ways that reflected the managing principles of the risk society. Postwar planning drew upon and constituted new areas of activity for government and community agencies, creating opportunities for the deployment of knowledge-practices such as personnel selection while opening up the interior of the subject as an object of governance, by assessing and calibrating allegedly innate human capacities.
Keywords: Domesticity; Education; Employment and training policies; Social sciences; Welfare state; Women